Beyond arsenite: Arsenite-oxidizing prokaryotes drive sulfur compound oxidation - Chengsheng Yang; Yifan Xu; Yao Nie; Yang Li; Xian-Chun Zeng (Bioresource Technology, 2027)

Multiple generations of kyanite recorded in migmatitic gneiss from the island of Fjørtoft, Western Gneiss Region, Norway - Yuan-Yuan Li; Hai-Jun Xu; Qiong-Xia Xia; Chun-Li Zheng; Peng-Lei Liu (Lithos, 2026)

Experimental study on evaporation characteristics of liquids in a bottom-heated cylindrical pool under low-pressure environment - Xu-Ge Wang; Chuan-Long Ge; Chun-Mei Wu; You-Rong Li (Desalination, 2026)

Secondary metabolites from the heartwood of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Cai-Wen Meng; Chun-Zhi Zhao; Jie Liu; Wen-Jing Zu; Hong-Yun Bai; Jian-Yu Liu; Yong-Nan Xu; Mei-Chen Li (Biochemical Systematics and Ecology, 2026)

Inverse design of multi-frequency bandgaps for multi-modal vibration control in long-span bridge cables - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

A covalent organic framework with hydrazone bond for efficient enrichment of phenolic pollutants - Xiaohua Xu; Lin Hao; Weihua Liu; Qianqian Wang; Shuofeng Li; Qiuhua Wu; Chun Wang; Zhi Wang (Food Chemistry, 2026)

Composite microbial inoculants regulate community assembly to reduce nitrogen loss during biodrying-composting process - Yingjie Liu; Haimin Li; Wanting Li; Yanting Chen; Zitong Kang; Zhi Xu; Yuquan Wei; Bo Wang; Guo-chun Ding; Ji Li (Environmental Research, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Coumarin constituents from Gerbera delavayi: Anti-inflammatory and anti-tumor activities with chemotaxonomic significance - Yan Zhong; Yu-Shuang Wen; Ying-Jie Xu; Chun-Hua Liu; Xue Ma; Yong-Lin Wang; Yong-Jun Li; Li Jiang (Biochemical Systematics and Ecology, 2026)

Chemical constituents from the root of Bistorta suffulta (Maxim.) H. Gross and their chemotaxonomic significance - Xin-Yi Liu; Chun-Yi Li; Meng-Yin Luo; Xu Yang; Lu-Jun Li; Li-Juan Sun; Chun-Yang Shi (Biochemical Systematics and Ecology, 2026)

P-wave velocity structure of the Zhongnan Fault and Ridge Zone between two sub-basins of the South China Sea - Wang Li; Chun-Feng Li; Yongjian Yao; Min Xu; Chuanhai Yu; Yongkang Deng; Ming Yang; Jinwei Gao (Tectonophysics, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Cr(VI) stress induces carbon-nitrogen metabolic reprogramming in Penicillium oxalicum SL2 - Yating Luo; Yifan Yang; Yezi Fang; Xiuya Xu; Chun Zhang; Jing Li; Ting Guo; Jiyan Shi; Haibo Zhang (Journal of Hazardous Materials, 2026)

Molecularly imprinted boronic acid-functionalized covalent organic frameworks for ultrasensitive detection of bisphenol pollutants and ecological risk evaluation - Yuanyuan Wan; Chun Liu; Xinru Li; Yuanguang Zhou; Zhimin Liu; Zhigang Xu (Journal of Hazardous Materials, 2026)

The antiviral effect of TRPV1 antagonist SB-705498 against GCRV infection via inflammation and apoptosis inhibition - Wei Wang; Ziyu Xie; Yang Xu; Jing Liu; Haoyang Xia; Chunya Wu; Liang Hu; Yanxia Jiang; Chun Li; Junhua Li; Xinyu Liang (Fish & Shellfish Immunology, 2026)

Rare earth Ce3+/Ce4+ redox effect coupled S-scheme heterojunction synergistically boost electron transfer for efficient photocatalytic environmental remediation - Dongyu Xu; Jiangyu Wang; Pengshuai Yin; Jing Zhang; Situ Mu; Li He; Chun Liu (Environmental Research, 2026)

Buckling behavior of cruciform-section thin concrete encased steel column under axial load - Wei Zhou; Xue-Chun Liu; Xu-Ze Feng; Senping Wang; Yapeng Li (Engineering Structures, 2026)

Slab flattening in the mantle transition zone drives extrusion and upwelling of ancient subducted material - Liang Zhou; Hong-Yan Li; Bo Pan; Zhong-Hai Li; Yangfan Deng; Shui-Jiong Wang; Chun Yang; Yi-Gang Xu (Earth and Planetary Science Letters, 2026)

Periphyton plays a dual role in the bioavailability of organic phosphorus in aquatic environments - Cong-min Wu; Ren-yong Shi; Yuan-chun Yu; Xin-yu Hu; Ernest Uwiringiyimana; Jiu-yu Li; Ren-kou Xu (Applied Geochemistry, 2026)

Granulosa cell dysfunction is associated with MCU-mediated mitochondrial calcium dyshomeostasis and reduced AKT phosphorylation in porcine cystic follicles - Yan-Zhu Chen; Ya-Nan Sun; Bo-Qi Zhang; Jin-Xin Zong; Yu-Xin Luo; Si-Hui Wang; Ya-Qiu Li; Hong Hao; Xu Zhou; Lu Chen; Chun-Jin Li (Theriogenology, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Investigation of the coupled dynamics and response correlations of a 10-MW Triple-spar floating offshore wind turbine under variable wind-wave-current conditions - Dinghong Lu; Zifei Xu; Haoda Huang; Qingsong Liu; Yangtian Yan; Weipao Miao; Chun Li; Minnan Yue (Ocean Engineering, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Tuned pile vibration isolation method for near-field rail transit based on the negative effective mass density model for a dual-resonator system - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Thermally buffered remnant melts sustain explosivity after caldera collapse: Cryptotephra evidence from Aira, Japan - Xuan-Yu Chen; Yi-Gang Xu; Xiao-Long Huang; Ji-Hoon Kim; Shuang Yan; Peng-Li He; Myong-Ho Park; Jong-Hwa Chun (Earth and Planetary Science Letters, 2026)

Polystyrene nanoparticles stimulate the growth and microcystin synthesis of Microcystis aeruginosa - Kui Xu; Jiaqi Tao; Zhen Chen; Xiafei Zheng; Yong Zhang; Zhengke Li; Chun Chen; Chunmei Zhang; Xiongwen Chen; Philippe Juneau; Zhili He (Aquatic Toxicology, 2026)

The effect of arbuscular mycorrhizal fungi on the physiological and biochemical functioning of the ornamental species Catalpa bungei against Meloidogyne incognita - Zhen-Hui Wang; Xue-Li Mou; Pan-Pan Meng; Gui-Hua Meng; Wei Chen; Xia-An Tang; Ke-Xu Xin; Yi Zhang; Chun-Yan Wang (European Journal of Plant Pathology, 2026)

Transcriptomic analysis reveals organ-specific adaptations in the gut-liver axis during diet domestication of mandarin fish (Siniperca chuatsi) - Hao-Yu Li; Zhi-Guang Hou; Yi-Huan Xu; Cheng-Bin Wu; Zun-Li Qi; Xiao-Wei Gao; Chun‑Long Zhao; Xin Zhao; Li-Han Zhang (Aquaculture International, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

K-feldspar oscillatory zoning constraining efficient crystal fractionation in high-silica magma: A case study of the Dacaowu pluton, eastern China - De-Zhou Chen; Jian Li; Ming-Chun Song; Wen-Yan Cai; Chao Zhang; Zheng-Yang Zhang; Xu-Yan Bian (Journal of Geochemical Exploration, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

Functional Characterization of CLE Peptides in Cotton Root Development Reveals GhCLE47 as a Key Regulator of Auxin-Mediated Root Architecture - Gai-Yuan Hu; Peng Liao; Xin-Yao Jiang; Ying-Chao Tang; Ting-Wan Li; Yang Li; Fu-Chun Xu; Zhen-Nan Zhang (Journal of Plant Growth Regulation, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Evaluation of Zanthoxylum bungeanum sprouts amino acids profile by capillary electrophoresis and principal component analysis - Chun-Mei Lv; Wen-Juan Shi; Xu-Kun Zhou; Wei-Feng Wang; Jun-Li Yang (Food Chemistry, 2026)

Broad-spectrum antiviral activity of molnupiravir against fish rhabdoviruses through entry blockade and induced viral mutagenesis - Jing-Zhuang Zhao; Chun-yan Guan; Yi-Zhi Shao; Wei-Tong Liu; Tong-Yan Lu; Li-Ming Xu (Fish & Shellfish Immunology, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Modal parameters identification of highly non-orthogonal structures based on curve fitting frequency domain decomposition method - Yu-Fei Liu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Bing-Zhe Zhai (Engineering Structures, 2026)

Control of mantle infertility on cross-arc geochemical diversity revealed by zinc isotope systematics - Chun Yang; Hong-Yan Li; Sheng-Ao Liu; Yoshihiko Tamura; Sergey Smirnov; Jeffrey G. Ryan; Yi-Gang Xu (Earth and Planetary Science Letters, 2026)

Pt(II) complexes with narrow-spectrum emission for high-performance green organic light-emitting diodes - Qinghua Xia; Yong Cao; Yihan Chu; Yang Li; Xuanbo Hu; Jinyu Song; Cong Zhang; Xiao-Chun Hang; Lin Xu (Chemical Engineering Journal, 2026)

The Dorsal CA2 to Ventral CA1 Circuit Contributes to Spatial and Context-Dependent Memories - Ning Li; Bingqing Zhao; Xiaowen Shen; Hua He; Jianxiang Zhou; Jing Zhang; Lin Xu; Xiaochun Chen; Chun Xu (Neuroscience Bulletin, 2026)

Biological Mechanisms of Phosphorus Mobilization in Long-term and Short-term Tea–White Clover Intercropping Systems on Red Acidic Soils - Ya Chen; Pei Yuan; Chun Wang; Yingzi Wang; Dandan Xu; Mamdouh A. Eissa; Ghulam Mustafa Shah; Jinjing Li; Shuaiming Li; Zeyu Zhong; Chang Tian (Journal of Soil Science and Plant Nutrition, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Knockdown of Long Non-coding RNA-MALAT1 Ameliorates Diabetic Lower Limb Atherosclerotic Disease Through MiR-17-5p-Mediated Endothelial Cell Pyroptosis - Juan Li; Jia-Xin Xu; Chun Wang; Fang-Fang Zhu (Biochemical Genetics, 2026)

Interfacial processes and biogeochemical cycling of plutonium in environmental media: Sources, transformation, and impacts - Chun Zhang; Xiang Zhou; Hao Sun; Zengyan Li; Yu Wang; Jia Zhan; Weixian Wang; Hui Xu (Journal of Environmental Radioactivity, 2026)

Thermal and energy saving performance of photovoltaic-green roof: An experimental and modeling study in hot summer and cold winter area - Yang He; Zhicheng Duan; Mengjie Song; Mengmeng Dai; Xi Zhang; Yulu Chen; Chaoen Li; Lei Xu; Yijun Lu; Chun Liang Tan; Jianlin Liu (Energy and Buildings, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Three-dimensional cell culture in vitro could better recapitulate the biological behavior of cells in vivo - Zhihao Qi; Shuhua Yang; Chun Fu; Junjie Xu; Quan Li; Junfang Yan; Aihua Shen; Burong Hu (Tissue and Cell, 2026)

Multi-stage pretreatment coupled with microwave-assisted formic acid hydrolysis for green preparation of xylose residue-based cellulose nanofibers - Haolong Zhang; Wenjing Bu; Ruimin Guo; Sai Zhang; Kai Fu; Zhining Li; Guizhuan Xu; Xiaoyang Zheng; Wei Chen; Chun Chang (Sustainable Chemistry and Pharmacy, 2026)

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

Plant–microbe interactions underpin contrasting enzymatic responses to flooding intensity variation in the cascade reservoir riparian areas - Nan-ping Wu; Shan-ze Li; Kailang Yin; Yu-chun Wang; Zheng Sun; Xuming Xu; Qingkong Chen; Yufei Bao; Jie Wen (CATENA, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Cu-catalyzed deaminative thiocyanation of anilines via nitrate reduction - Yong-Sheng Zhou; Yan Yang; Jing-Yao Zhou; Li-Jun Xu; Yi-Xie Tan; Xin-Chun Zhang; Liang Wang (Molecular Diversity, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Multiscale analysis of mycotoxin accumulation in fungal-infected maize using hyperspectral imaging and electron microscopy - Lili Cao; Jie Li; Jing Yu; Jiaqi Zhou; Chun Gao; Li Xu; Shaotong Jiang; Min Pang (Journal of Cereal Science, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Endothelial GATAD1 Exacerbates Blood-brain Barrier Dysfunction in Ischemic Stroke through Caveolae-mediated Transcytosis - Lizhen Fan; Hui Liu; Shanshan Li; Lingling Li; Zhi Zhang; Pinyi Liu; Haiyan Yang; Shengnan Xia; Xiang Cao; Chun Wang; Yun Xu (Neuroscience Bulletin, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

Mechanism of baicalein from Wudang Mountain Scutellaria baicalensis Georgi. against atopic dermatitis based on network pharmacology, transcriptomics and in vitro experimental validation - Liu Tang; Gang Liu; Dan Li; Tianshuai Wang; Chun Wang; Guangwen Luo; Rui Peng; Xu Cai (Natural Product Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Phragmalin-type limonoid orthoesters from the twigs and leaves of Khaya ivorensis and their cytotoxic activities - Zong-Yi Zhang; Jia-Nan Wang; Peng Sun; Xiao-Cui Shi; Yi-Dian Xiao; Kai-Long Ji; Chun-Fen Xiao; Xiao-Nian Li; You-Kai Xu; Dong-Hua Cao (Phytochemistry, 2026)

Experimental study on pore structure and permeability of different rank coals related to temperature - Yina Yu; Zhaoping Meng; JiangJiang Li; Yixin Lu; Chun Xu; Yuhen Wang (Fuel, 2026)

Characterization and influencing factors of hydroxymethanesulfonate (HMS) in the North China plain: integration of field measurements and theoretical calculations - Chun Chen; Haijie Zhang; Yele Sun; Junling Li; Zhiqiang Zhang; Jian Gao; Rui Gao; Lianfang Wei; Nan Ma; Wanyun Xu; Pingqing Fu (Atmospheric Environment, 2026)

PbrRALF5/10 prevents incompatible pollen tube death by reconstructing the methyl-esterified pectin and reactive oxygen species metabolism of pear in vitro - Xiao-Xiong Kong; Tao Chen; Li-Yu Gao; Xu Huang; Xiao Liu; Jing Zhang; Zhi-Ping Zhang; Chun-Lei Wang (Plant Molecular Biology, 2026)

Different efficiency of Orange Carotenoid Protein (OCP)-related quenching during high light regulation of two cyanobacterial species - Kui Xu; Shiquan Tang; Chun Chen; Yong Zhang; Zhengke Li; Zhen Chen; Weizhi Li; Xiongwen Chen; Philippe Juneau (Photosynthesis Research, 2026)

System-dependent divergence of microbial community and resistome in two anaerobic niches under sulfamethoxazole selection - Yuepeng Deng; Depeng Wang; Jie Li; Junbo Tang; Sifang Wang; Zhu Wang; Chun Hu; Xu-Xiang Zhang (Water Research, 2026)

Efficient biosynthesis of retinal from Escherichia coli by metabolic engineering - Chun-Li Liu; Guangbo Xu; Eric Fordjour; Linhua Zhao; Yankun Yang; Xiuxia Liu; Zhonghu Bai (Bioresource Technology, 2026)

Study on Aeromagnetic Anomaly Characteristics and Tectonic Ore-Controlling Effects in Leiwuqi-Zuogong Area, Tibet - Jian-chun Xu; Yan-xu Liu; Wen-yong Li; An-qi Cao; Shan Gao; Xue Yang (Applied Geophysics, 2025)

Developing sewage sludge hydrochar-based wood bio-adhesives: the role of oxidized lignin-containing cellulose nanofiber - Ze-Kai Tan; Han-Song Zhu; Fei Feng; Zu-Guo Yang; Li-Chun Dai; Zhi-Xiang Xu (Sustainable Chemistry and Pharmacy, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Toonasinetins A and B, two new compounds from the branches and leaves of Toona sinensis - Nai-Dong Li; Cheng-Shan Wei; Chun-Xia Song; Chun-Jiang Du; Juan Xu (Phytochemistry Letters, 2025)

Tailored magnetic ZIF-67-derived FeCo-LDH for PETase immobilization toward effective removal and biodegradation of high-crystallinity micro- and nano-PET - Yaxin Chen; Yixiang Xu; Yanhong Zhou; Zhou Deng; Yu Feng; Ruifang Zhang; Chun Yang; Hongchun Li; Haibo Yu; Guangya Zhang (Journal of Hazardous Materials, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

RGB-based combustion state classification and stability analysis of SOFC afterburner: effects of fuel utilization and steam-to-carbon ratio - Jingjing Wang; Shuyu Zhang; Jingang Lai; Jiashu Jin; Chun Zou; Jung-Sik Kim; Zhonghua Deng; Yuanwu Xu; Xi Li (Fuel, 2025)

Study on the effect of glycerol monostearate on the properties of sesame oil body-based aerated emulsions and related mechanisms - Delong Li; Yanpeng Zhang; Yue Long; Kun Zhang; Wei Xu; Chun Hu; Hailong Zhang (Food Chemistry, 2025)

Discovery and validation of novel neuroprotective peptides from black soybean protein hydrolysates: Dual targeting of cholinergic dysfunction and oxidative stress - Lulu Li; Yang Yang; Bing Wang; Yue Xu; Yan Wang; Xiao-fei Liu; Guang Zhang; Chun-min Ma; Na Zhang (Food Bioscience, 2025)

Biobased phase change material packaging for dark chocolate: Enhanced thermal management against temperature fluctuations - Qianzhu Zhao; Siew-Yee Wong; Yu Zhang; Poh-Chong Lim; Vinod Kumar Sivaraja; Andrew Chun-Yong Ngo; Weibiao Zhou; Xu Li (Food Packaging and Shelf Life, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

How does built environment influence the spatial distribution of road carbon emission: Mitigation or exacerbation? - Xuexian Xu; Liyuan Zhao; Zhi-Chun Li; Qing Ma (Sustainable Cities and Society, 2025)

Green fabrication of diazo-coupled porous polymer as solid-phase extraction adsorbent coupled with HPLC-MS for sensitive detection of phenolic endocrine disruptors in pork and carp - Ziqi Xu; Xiaocui Chen; Zhi Li; Qianqian Wang; Chun Wang; Qiuhua Wu (Food Chemistry, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Identification and functional characterization of Cyprinus carpio cGAS reveals its pivotal role against viral infection - Chun Li; Guoli Hou; Liang Hu; Yang Xu; Qiushi Zhang; Xinyu Liang; Yong-An Zhang; Junhua Li (Fish & Shellfish Immunology, 2025)

A novel strain-based deformation monitoring method for subsea free-spanning pipelines - Tao Jiang; Zi-min Xie; Jia-jian Wang; Dong-sheng Li; Chun-xu Qu (Engineering Structures, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

A novel acoustic barrier based on Chladni patterns and its optimal design - Qiao-Yun Wu; Qing-Jing Li; Lan Ding; Zhi-Feng Xu; Chun-Feng Zhao (Building and Environment, 2025)

Correlation between intestinal microbiota composition and growth performance in largemouth bass (Micropterus salmoides) - Dong dong Yu; You xing Xu; Xing han He; Xian ke Zhou; Dong chun Li; Shun Yang; Hui Fei (Aquaculture International, 2025)

Comparative transcriptomic analysis of gill tissues in largemouth bass (Micropterus salmoides) under low-temperature stress - Zhi-Guang Hou; Meng-Chao Xing; Li-Han Zhang; Yi-Huan Xu; Xin Zhao; Xiao-Wei Gao; Chun-Long Zhao; Cheng-Bin Wu (Aquaculture International, 2025)

Harnessing transposable elements for plant functional genomics and genome engineering - Xiao-Yuan Tao; Shou-Li Feng; Lu Yuan; Yan-Jun Li; Xin-Jia Li; Xue-Ying Guan; Zhong-Hua Chen; Sheng-Chun Xu (Trends in Plant Science, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Deep carbon sink in the East Asian mantle and its impact on atmospheric CO2 drawdown since the Cretaceous - Chun Yang; Sheng-Ao Liu; Hong-Yan Li; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Influx of Metabolites into Cerebrospinal Fluid in Intracerebral Hemorrhage is Associated with Increased Central Inflammation: a Retrospective Observational Study - Huaying Zhang; Yuxia Zhong; Jinlian Shao; Kaijian Sun; Lingling Zhang; Yulong Zhang; Yu Xiao; Xiangyu Zuo; Zhixin Li; Tianhui Zeng; Zizheng Gao; Chun Yang; et al. (Translational Stroke Research, 2025)

First report on trait segregation in F1 hybrids between the cultivated peanut (Arachis hypogaea L.) and the wild incompatible species A. glabrata Benth. - Wei Jie Qi; Hao Jie Sun; Jing Yu; Chun Jiao Jiang; Guang Di Yuan; Shang Xia Li; Chun Yan Xu; Chuan Tang Wang (Genetic Resources and Crop Evolution, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Vibration isolation method based on local resonance mechanism for near-field piling in rail transport - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Soil Dynamics and Earthquake Engineering, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Seismic performance of thin-flexible PEC column and H-section beam with end-plate connection joints - Wei Zhou; Kun Zhang; Bu-Shuan Li; Gen-Tian Zhao; Xue-Chun Liu; Xu-Ze Feng (Engineering Structures, 2025)

Typhoon fragility analysis of transmission tower-line system considering wind-induced fatigue - Jia-Xiang Li; Tong Yang; Chao Zhang; Li Sun; Chun-Xu Qu (Engineering Structures, 2025)

Delivery of penetration-enhancing antioxidant polyphenol nanoparticles with Codonopsis pilosula polysaccharide microneedles for synergistic treatment of psoriasis - Siqi Liu; Silu Song; Yu Zhang; Liming Yan; Yuhui Chen; Wanrong Li; Banaz Jalil; Chun Wu; Yuping Fu; Xingfu Chen; Jingyi Gu; Lixia Li; et al. (Carbohydrate Polymers, 2025)

Luteolin prevents axitinib-induced kidney damage in mice - Na Niu; Xu Li; Dong Tang; Tian-Qing Jin; Si-Wen Ji; Chun-Lei Yu; Yong Li (Chemico-Biological Interactions, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Flow Control-Based Aerodynamic Enhancement of Vertical Axis Wind Turbines for Offshore Renewable Energy Deployment - Huahao Ou; Qiang Zhang; Chun Li; Dinghong Lu; Weipao Miao; Huanhuan Li; Zifei Xu (Journal of Marine Science and Engineering, 2025)
As wind energy development continues to expand toward nearshore and deep-sea regions, enhancing the aerodynamic efficiency of vertical axis wind turbines (VAWTs) in complex marine environments has become a critical challenge. To address this, a composite flow control strategy combining leading-edge suction and trailing-edge gurney flap is proposed. A two-dimensional unsteady numerical simulation framework is established based on CFD and the four-equation Transition SST (TSST) transition model. The key control parameters, including the suction slot position and width as well as the gurney flap height and width, are systematically optimized through orthogonal experimental design. The aerodynamic performance under single (suction or gurney flap) and composite control schemes is comprehensively evaluated. Results show that leading-edge suction effectively delays flow separation, while the gurney flap improves aerodynamic characteristics in the downwind region. Their synergistic effect significantly suppresses blade load fluctuations and enhances the wake structure, thereby improving wind energy capture. Compared to all other configurations, including suction-only and gurney flap-only blades, the composite control blade achieves the most significant increase in power coefficient across the entire tip speed ratio range, with an average improvement of 67.24%, demonstrating superior aerodynamic stability and strong potential for offshore applications.

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Pt decorated (CoMnFeCrNi)3O4 high-entropy oxide for low-temperature combustion of C3H8 - Lihong Xie; Yaohun Dun; Qiji Wang; Jie Xu; Song Li; Rong Chen; Chun Du; Bin Shan (Fuel, 2025)

Prussian blue anchored Fe(Ⅲ)-Tannic acid composite-mediated colorimetric and photothermal dual-mode immunosensor for the detection of tetrodotoxin - Sayed Haidar Abbas Raza; Bao-Zhu Jia; Jing-Min Li; Qin-Chun Yin; Wu-Yi Zhou; Sameer D. Pant; Hongtao Lei; Zhen-Lin Xu; Lin Luo (Food Control, 2025)

Emerging Trends and Hot Spots in Epigenetic Modifications in Neurology: A Bibliometric Analysis - Shu-Ying Xu; Siyao Zhang; Chun-Li Zeng; Yong-Jun Peng; Min Xu (Molecular Neurobiology, 2025)

Influence of Geometric Effects on Dynamic Stall in Darrieus-Type Vertical-Axis Wind Turbines for Offshore Renewable Applications - Qiang Zhang; Weipao Miao; Kaicheng Zhao; Chun Li; Linsen Chang; Minnan Yue; Zifei Xu (Journal of Marine Science and Engineering, 2025)
The offshore implementation of vertical-axis wind turbines (VAWTs) presents a promising new paradigm for advancing marine wind energy utilization, owing to their omnidirectional wind acceptance, compact structural design, and potential for lower maintenance costs. However, VAWTs still face major aerodynamic challenges, particularly due to the pitching motion, where the angle of attack varies cyclically with the blade azimuth. This leads to strong unsteady effects and susceptibility to dynamic stalls, which significantly degrade aerodynamic performance. To address these unresolved issues, this study conducts a comprehensive investigation into the dynamic stall behavior and wake vortex evolution induced by Darrieus-type pitching motion (DPM). Quasi-three-dimensional CFD simulations are performed to explore how variations in blade geometry influence aerodynamic responses under unsteady DPM conditions. To efficiently analyze geometric sensitivity, a surrogate model based on a radial basis function neural network is constructed, enabling fast aerodynamic predictions. Sensitivity analysis identifies the curvature near the maximum thickness and the deflection angle of the trailing edge as the most influential geometric parameters affecting lift and stall behavior, while the blade thickness is shown to strongly impact the moment coefficient. These insights emphasize the pivotal role of blade shape optimization in enhancing aerodynamic performance under inherently unsteady VAWT operating conditions.

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Microbial reductive mobilization of As(V) in solid phase coupled with the oxidation of sulfur compounds: An overlooked biogeochemical reaction affecting the formation of arsenic-contaminated groundwater - Chengsheng Yang; Yifan Xu; Tingting Yu; Yang Li; Xian-Chun Zeng (Journal of Hazardous Materials, 2025)

Experimental and mechanistic study on liquid–liquid equilibrium for the separation of cyclohexane and ethyl acetate using imidazolium ionic liquids - Xia Li; Shuyan Liu; Yahui Yin; Weilian Zhang; Chenglong Sun; Zilong Yu; Yu Zhou; Chun Zhao; Zhiguo Liu; Hongfei Xiang; Xianzhen Xu (Fuel, 2025)

Transcriptomic Response Pathways of Yeast to Crucial Polyphenolic Acids in Rosmarinus Acid Biosynthesis - Tao Xu; Jun-lu Duan; Samuel Ntakirutimana; Li Wang; Zhi-Hua Liu; Chun Li; Bing-Zhi Li (Current Microbiology, 2025)

Metabolomic analysis of blood spots in a Chinese cohort with autism spectrum disorders: a pilot study - Hui Wang; Li Ding; Zheng-huan Mao; Yu Du; Qing-mei Han; Jia-yu Xu; Fei-fei Peng; Hai-feng Li; Chao-chun Zou (Metabolic Brain Disease, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

The microbiome, metabolome, and correlation analysis reveal the beneficial role of the commensal Shewanella sp. MR-7 in foodborne enteritis in turbot (Scophthalmus maximus L.) - Chao-Qun Li; Wen-Yi Wang; Xin Wen; Si-Yu Qi; Jia-Ning Xu; Dan-Yu Wu; Kang-Di Tian; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2025)

Geochemical evidence of paleo-pacific slab melting in the big mantle wedge beneath Northeast China during the Early Cretaceous - Chao-Yang Liu; Hong-Yan Li; Yi-Gang Xu; Qiang Ma; Chun Yang; Wan-Feng Zhang (Chemical Geology, 2025)

G protein-coupled receptor GPR182 negatively regulates sprouting angiogenesis via modulating CXCL12-CXCR4 axis signaling - Changsheng Chen; Wei Liu; Fang Yuan; Xiaoning Wang; Xi Xu; Chang Chun Ling; Xiaojuan Ge; Xiaozhong Shen; Bowen Li; Yuqian Shen; Dong Liu (Angiogenesis, 2025)
Angiogenesis is a critical process for tumor progression, regulated by various signaling pathways. Although antiangiogenic therapies targeting the VEGF pathway have shown potential, their effectiveness is inconsistent across different tumor types. GPR182, an endothelial cell-specific G protein-coupled receptor, is frequently downregulated in hypervascular tumors, but its specific role in angiogenesis has not been well defined. Our study reveals that GPR182 expression is markedly reduced in hepatocellular carcinoma (HCC) and inversely correlates with CD31, a pan-endothelial marker. In zebrafish embryos, Gpr182 deficiency resulted in enhanced angiogenic sprouting and hypervascularization, and GPR182-deficient human umbilical vein endothelial cells (HUVECs) showed increased migration and proliferation. At the molecular level, GPR182 acts as a decoy receptor, binding CXCL12 and regulating its gradient, which in turn suppresses CXCR4-mediated angiogenesis. The pharmacological blockade of CXCR4 with AMD3100 corrected the abnormal angiogenic phenotype in Gpr182-deficient zebrafish embryos and in the livers of a zebrafish HCC model. This work uncovers GPR182 as a negative regulator of angiogenesis, a key process in tumor growth and metastasis, and proposes that targeting GPR182 may offer a novel therapeutic approach for antiangiogenic strategies in cancer treatment.

Pronounced advance on typhoon track forecast with global convection-permitting model - Jun Gu; Chun Zhao; Gudongze Li; Jiawang Feng; Mingyue Xu; Qiuyan Du; Zihan Xia; Yubin Li; Guanghua Chen; Xiaoyu Hao; Junshi Chen; Hong An (Science Bulletin, 2025)

Self-propagated clonal seed production in dicotyledonous Arabidopsis - Wen-Qiang Chen; Liping Xu; Yuchun Rao; Chaolei Liu; Zhengyuan Hong; Hongwei Lu; Chun-Ming Liu; Hong-Ju Li; Kejian Wang (Science Bulletin, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

ZnAl alloy and organosulfur hybrid energy storage for long term cyclability - Qing Liu; Zhiyong Zheng; Chun Huang; Gun Jang; Qingyun Dou; Yong Li; Shengyang Huang; Baohuai Zhao; Yongan Wu; Yi Zhang; Bo-Kyong Kim; Xu Yu; et al. (Chemical Engineering Journal, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Correction to: A Virtual Reality Platform for Context-Dependent Cognitive Research in Rodents - Xue-Tong Qu; Jin-Ni Wu; Yunqing Wen; Long Chen; Shi-Lei Lv; Li Liu; Li-Jie Zhan; Tian-Yi Liu; Hua He; Yu Liu; Chun Xu (Neuroscience Bulletin, 2025)

Monitoring the level of hydrogen sulfide in arthritis and its treatment with a novel near-infrared fluorescent probe - Jing-Jing Chao; Ling Hu; Jing-Fang Mi; Guo-Jiang Mao; Fen Xu; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Milk-derived exosome nanovesicles: recent progress and daunting hurdles - Kaili Wang; Xu Zhao; Sijia Yang; Xiaoxi Qi; Guofang Zang; Chun Li; Aili Li; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2025)

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

Anti-neuroinflammatory terpenes from Magnolia grandiflora - Ding-Xun Wu; Jue Yang; Li-Hua Chen; Shuang-Yu Xu; Jun Jin; Ya-Nan Li; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry, 2025)

Does digital government reduce carbon emissions? Empirical evidence from global sources - Chun Li; Xu Chen; ChenXi Yuan (Journal of Environmental Management, 2025)

Nitrate nitrogen concentrations drive microbial community composition and functional responses in microplastic surface biofilms - Shuangshuang Li; Yu Zheng; Chun Wang; Duo Xu; Heng Liu; Yan Song (Journal of Environmental Chemical Engineering, 2025)

Study on vapor–liquid equilibrium for the separation of ethyl acetate and isopropanol azeotrope using phosphonium-based ionic liquids - Yahui Yin; Shuyan Liu; Xia Li; Zilong Yu; Weilian Zhang; Chenglong Sun; Chun Zhao; Xianzhen Xu (Fuel, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Increase of ATP synthesis and amino acids absorption contributes to cold adaptation in Antarctic bacterium Poseidonibacter antarcticus SM1702T - Wen-Yue Xu; Sha-Sha Liu; Xiao-Han Guo; Peng Wang; Chun-Yang Li; Li Liao; Qi-Long Qin (Extremophiles, 2025)

Elucidating Secondary Organic Aerosol Processes through High-Resolution Aerosol Mass Spectrometry in Beijing - Weiqi Xu; Chun Chen; Zhijie Li; Zhiqiang Zhang; Yu Zhang; Zifa Wang; Yele Sun (Advances in Atmospheric Sciences, 2025)

Two-stage anomaly detection for imbalanced bridge data by attention mechanism optimisation and small sample augmentation - Chun-Xu Qu; Yun-Tao Yang; Hong-Ming Zhang; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2025)

Morphology and molecular analysis of Heterodera camelliae n. sp. (Nematoda: Heteroderinae), a new species of cyst‑forming nematode parasitizing tea plants in China - Chun-Hui Ni; Qian-Ying Li; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

Double enzyme enhanced microbial induction of carbonate precipitation (E-MICP) to improve mechanical properties of sandy soil and its biocementation mechanism - Lei Niu; Yao-ting Duan; Xin Xu; Xiao-yan Wu; Zhe Wang; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2025)

Characterization and application of Schizochytrium sp. HX-308 promoters for enhanced docosahexaenoic acid biosynthesis - Chun-Xiao Yan; Yi Zheng; Shuai Zhang; Zi-Jia Li; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Molecular insights of T-2 toxin exposure-induced neurotoxicity and the neuroprotective effect of dimethyl fumarate - Xingyao Pei; Shuhui Ma; Liang Hong; Zonghui Zuo; Gang Xu; Chun Chen; Yao Shen; Dingkuo Liu; Cun Li; Daowen Li (Food and Chemical Toxicology, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Frontier fabrication of silicon-based anodes: Synergistic enhancement of structural integrity and conductivity - Yin Yang; Hongmei Song; Jian Wang; Dong Sun; Yulong Li; Changbo Lu; Chun Lu; Jinsen Gao; Chunming Xu; Jun Xu; Yongfeng Li; Xinlong Ma (Chemical Engineering Journal, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Prediction on seismic performance levels of reinforced concrete beams by considering crack development - Chao Ma; Jing-wei Chi; Dong-xu Li; Fan-chao Kong; De-chun Lu; Wei-zhang Liao (Soil Dynamics and Earthquake Engineering, 2024)

Comprehensive understanding the impacts of polyethylene microplastics (PE-MPs) on freshwater biofilms: Tracking from growth, microbial community structure to element metabolisms - Shuangshuang Li; Mingcan Cai; Yu Zheng; Duo Xu; Heng Liu; Yan Song; Chun Wang (Journal of Water Process Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Structural damping ratio identification with iterative compensation for spectral leakage errors using frequency domain decomposition - Chun-Xu Qu; Yu-Fei Liu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2024)

Atmosphere-driven oriental regulation of Ru valence for boosting alkaline water electrolysis - Na Xu; Man-Man Li; Hai-Yi Sun; Guodong Li; Xin Wen; Denghao Ouyang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Lathyrane diterpenoids from Euphorbia lathyris induce cell-cycle arrest and apoptosis in human hypertrophic scar cells - Chun-Yan Zhang; Shun Xu; Lei Yu; Yi-Wen Nie; Si-Bo Li; Jian-Yong Zhu (Natural Product Research, 2024)

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Heterogeneous marine environments diversify microbial-driven polymetallic nodule formation in the South China Sea - Mingyan Lai; Qian Liu; Xiaogu Wang; Dong Sun; Lihua Ran; Xiaohu Li; Chenghao Yang; Bo Lu; Xue-Wei Xu; Chun-Sheng Wang (Frontiers in Marine Science, 2024)
Most studies on the genesis of polymetallic nodules suggested that nodules in the South China Sea (SCS) are hydrogenetic; however, the complexity and the heterogeneity in hydrology and geochemistry of the SCS might cause different processes of nodule formation, impacting their application and economic value. Microbial-mediated ferromanganese deposition is an important process in nodule formation, but the related microbial potentials are still unclear in the SCS. In this study, we sampled in three typical regions (A, B, and C) of the SCS enriched with polymetallic nodules. Firstly, we investigated environmental and microbial characteristics of the water columns to determine the heterogeneity of upper seawater that directly influenced deep-sea environments. Then, microbial compositions and structures in sediment cores, overlying waters, and nodules (inside and outside) collected within the same region were analyzed for inferring features of nodule environments. Microbial interactions between nodules and surrounding environments were estimated with collinear network analysis. The microbial evidence indicated that geochemical characteristics in deep sea of the SCS that were key to the polymetallic nodule formation were severely affected by organic matter flux from upper water column. The sediment in region A was sub-oxic due to the large input of terrigenous and phytoplankton-derived organic matter, potentially enhancing the overflow of reduced metals from the porewater. The intense microbial interaction between nodules and surface sediment reinforced the origin of metals for the ferromanganese deposition from the sediment (diagenetic type). Contrarily, the sediments in regions B and C were relatively rich in oxygen, and metal ions could be majorly supplied from seawater (hydrogenetic type). The large discrepancy in microbial communities between nodule inside and remaining samples suggested that nodules experienced a long-term formation process, consistent with the feature of hydrogenetic nodules. Overall, distributions and interactions of microbial communities in nodules and surrounding environments significantly contributed to the nodule formation in the SCS by manipulating biogeochemical processes that eventually determined the source and the fate of metal ions.

Lateral transport facilitates terrestrial organic carbon burial in the Santa Barbara Basin over the past 80 years (1937–2018 CE) - Hanyue Xu; Da-Wei Li; Hong-Chun Li; William M. Berelson; Yang Ding; Li Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Pore evolution and reaction mechanism of coal under the combination of chemical activation and autothermal oxidation - Haihui Xin; Pengcheng Zhang; Jianguo Sun; Liang Lu; Chun Xu; Banghao Zhou; Hezi Wang; Yi Yang; Junzhe Li; Deming Wang (Fuel, 2024)

A high-permeability method for extracting purple yam saponins based on ultrasonic-assisted natural deep eutectic solvent - Yu-Jiao Hou; Peng-wei Wang; Han Zhang; Ying-Ying Fan; Xu Cao; Yan-Qiong Luo; Qian Li; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Highly efficient reduction of Cr(VI) from industries sewage using novel biomass-driven carbon dots modified TiO2 under sunlight - Ruoxin Ma; Zijun Xu; Chun Zhang; Hao Li; Jiao Chen; Jingbiao Fan; Qingdong Shi (Chemical Engineering Journal, 2024)

Electrochemical advanced oxidation of per- and polyfluoroalkyl substances (PFASs): Development, challenges and perspectives - Xiaoyong Xu; Yang Li; Phong H.N. Vo; Pradeep Shukla; Lei Ge; Chun-Xia Zhao (Chemical Engineering Journal, 2024)

A tandem dual-pathway non-radical water purification simultaneously induced by single-molecule peroxymonosulfate with a catalyst of coexisting Cu single atoms and Fe3C nanoparticles - Shuaiqi Zhang; Zhihui Yin; Zhicong Lu; Zhe Xu; Chun Hu; Fan Li (Chemical Engineering Journal, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Efficient caproate production from lignocellulose via single-step electro-fermentation platform without organic electron donor - Yafei Zhang; Jianzheng Li; Xu Lian; Lin Li; Yang-chun Yong; Jia Meng (Bioresource Technology, 2024)

Phytochemical constituents from rhizomes of Dryopteris crassirhizoma and their anti-inflammatory activity - Xiao-Jun Li; Xiong-Hui Song; Si-Qi Tang; Kai-Xin Wei; Zong-Wu Suo; Yi Xu; Jiao Luo; Hao Huang; Chun-Ying Li; Dong-Xu Liu; Xiang-Qian Liu (Natural Product Research, 2024)

Silver nanoparticles exhibit ecotoxicological effects via oxidative stress, inflammation, and reproductive toxicity in Asian clam (Corbicula fluminea) - Chun Li; Zhiming Liu; Yang Xu; Jie Pi; Qiushi Zhang; Xiaoying Chen; Chengfeng Zhan; Liang Hu; Jibang Xie; Ziyu Xie; Xinlan Deng; Lixin Wen; et al. (Chemosphere, 2024)

Data-driven Bayesian Gaussian mixture optimized anchor box model for accurate and efficient detection of green citrus - Yunfeng Zhang; Li Li; Changpin Chun; Yifeng Wen; Congbo Li; Gang Xu (Computers and Electronics in Agriculture, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Effectiveness and mechanism of cyanide tailings cementation by steel slag coupled with non-ureolytic microbially induced carbonate precipitation - Yaoting Duan; Lei Niu; Yang He; Kai neng Lei; Xin Xu; Chun-li Zheng; Chunqiao Xiao (Process Safety and Environmental Protection, 2024)

Montmorillonite-coupled microbially induced carbonate precipitation (MICP) enhanced contaminant removal and carbon capture in cyanide tailings - Yaoting Duan; Lei Niu; Boxi Li; Yang He; Xin Xu; Caiqi Yu; Zhe Wang; Chunqiao Xiao; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2024)

Molecular simulation screening and sensory evaluation unearth a novel kokumi compound with bitter-masking effect: N-lauroyl-L-tryptophan - Lei Cai; Liyu Li; Xu Zhao; Lu Wang; Yuqin Cheng; Wenxiang Gao; Chun Cui (Food Chemistry, 2024)

Antibiotic resistance genes risks in relation to host pathogenicity and mobility in a typical hospital wastewater treatment process - Chenye Xu; Chun Hu; Fang Li; Weiping Liu; Yumin Xu; Dake Shi (Environmental Research, 2024)

Composition modulation of electrocatalysts based on 3d transition metal towards high-performance Zn-air batteries - Ya-Fei Guo; Xu Liu; Shao-Jie Yang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Chun-Sheng Li; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Measurement of 224Ra in water via pulsed ionization chamber (PIC) radon detector - Haowei Xu; Chunqian Li; Pengxia Liu; Wen Liu; Shibin Zhao; Natasha T. Dimova; Xiliang Cui; Lijun Song; Tianyi Zhu; Ergang Lian; Chun Xia; Yanming Xue; et al. (Journal of Environmental Radioactivity, 2024)

Anomaly detection of massive bridge monitoring data through multiple transfer learning with adaptively setting hyperparameters - Chun-Xu Qu; Hong-Ming Zhang; Ting-Hua Yi; Zhi-Yuan Pang; Hong-Nan Li (Engineering Structures, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Probing the AFF4–CCNT1 protein–protein interaction using a metal–organic conjugate for treating triple-negative breast cancer - Ying-Qi Song; Yiwen Xu; Li-Jun Yang; Ling Wang; Shaozhen Jing; Guan-Jun Yang; Daniel Shiu-Hin Chan; Chun-Yuen Wong; Wanhe Wang; Vincent Kam Wai Wong; Chung-Hang Leung (Chemical Engineering Journal, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

A DEM upscaling method with integrating valley lines based on HASM - Mingwei Zhao; Xiaoxiao Ju; Na Zhao; Chun Wang; Yan Xu; Xiaoran Wu; Weitao Li (Frontiers of Earth Science, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Innovative insights into dry fermented sausages flavor: Unraveling the impact of varied lactobacillus genera-driven fermentation - Sha-sha Zheng; Ying-ying Hu; Li-jun Tan; Liu Yang; Chun-yu Wang; Bao-cai Xu (Food Bioscience, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Magnetized bentonite modified rice straw biochar: Qualitative and quantitative analysis of Cd(II) adsorption mechanism - Shu-zhi Liu; Wei Ding; Hong-wei Zhang; Zhu-shuai Li; Ke-chun Tian; Ce Liu; Zeng-chao Geng; Chen-yang Xu (Chemosphere, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Effect of n-hexadecanoic acid on N2O emissions from vegetable soil and its synergism with Pseudomonas stutzeri NRCB010 - Huanhuan Zhang; Chun Hu; Linmei Li; Peng Lei; Weishou Shen; Hong Xu; Nan Gao (Applied Soil Ecology, 2024)

Biochar-derived dissolved organic matter enhanced the release of residual ciprofloxacin from the soil solid phase - Guo Chen; Jing Ma; Gang Yang; Chao Chen; Lulu Long; Linling Li; Li Gong; Min Xu; Jun Wu; Chun Song; Jiejie Lyu (Chemosphere, 2024)

Comparative analysis of the growth performance, vitality, body chemical composition and economic efficiency of the main cultivated strains of Pacific white shrimp (Litopenaeus vannamei) in coastal areas of China - Cheng Zhang; Chun-Yang Guo; Kai-He Shu; Shan-Liang Xu; Dan-Li Wang (Aquaculture, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Human health risk assessment and toxic effect of heavy metal(loid)s in Bamboo shoot products - Yu-Mei Xie; Meng-Yan Zhang; Fei-Peng Liu; Cheng-Chen Wang; Wen-Yuan Dong; Chun-Mei Xu; Xin Li; Wu-Mei Xu; Ping Xiang (Journal of Environmental Chemical Engineering, 2024)

C–C bond coupling differences between β-O-4 and 4-O-5 ether bonds over hydrophobic mesoporous Ru/MY-O catalysts: from lignin model compounds to polycyclic alkanes - Zhuang Li; Zi-Chun Fan; Xiang Bai; Xian-Yong Wei; Yierxiati. Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Jun-Long Wang; Xing Fan; Xiao-Yan He; Hai-Xu Zou; et al. (Fuel, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Condition assessment of stay cables using normalized sequence of vehicle-induced cable force peaks of stay cables on same side - Jin-Xin Li; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Qiang Han (Engineering Structures, 2024)

Early statin exposure influences cardiac and skeletal development with implications for ion channel transcriptomes in zebrafish - Ying Zhao; Hou-Zhi Yang; Huinan Li; Shuang Liang; Meng Wang; Chun-Di Li; Donghai Zhuo; Feifei Fan; Miao Guo; Xinxin Lv; Lingzhu Zhang; Xu Chen; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Promoting agricultural waste-driven denitrification and nitrogen sequestration with nano-enabled strategy - Chen Chen; Haiqing Gong; Yuquan Wei; Ting Xu; Ji Li; Guo-chun Ding (Bioresource Technology, 2024)

Application of multiple strategies to enhance oleanolic acid biosynthesis by engineered Saccharomyces cerevisiae - Xu Cheng; Yaru Pang; Yali Ban; Shuai Cui; Tao Shu; Bo Lv; Chun Li (Bioresource Technology, 2024)

Robustness of design flood estimates under nonstationary conditions: parameter sensitivity perspective - Bin Xiong; Shuchen Zheng; Qiumei Ma; Chun Fu; Tianfu Wen; Zhongzheng He; Lingqi Li; Chong-Yu Xu (Stochastic Environmental Research and Risk Assessment, 2024)
The changing frequency of flooding in global watersheds, driven by various human and natural factors like land use/cover changes and global warming, necessitates innovative approaches in flood frequency analysis and risk assessment. Nonetheless, the reliability of nonstationary frequency analysis models remains a concern given challenges in accurately measuring the uncertainty introduced by these methods and the impact on design flood values. In this study, deviation-based differential sensitivity indices, including single-parameter (SDDSI) and entire-parameter (EDDSI) measures were developed to assess the influence of parameter uncertainty in nonstationary models using Bayesian statistics and "equivalent reliability" nonstationary design. The Weihe River, the largest tributary of the Yellow River which is experiencing both climate change and heavy impact of human activities, is chosen to be the study area to investigate the impact of precipitation change and land use change on nonstationary flood frequency. Results show that in the One-At-A-Time (OAT) sensitivity analysis under a small uncertainty scenario (SUS) for parameter inputs, the shape parameter stands out as the most influential factor (SDDSI_SUS = 0.347) affecting the 100-year design flood in the Stationary Generalized Extreme Value (SGEV) model. For the Non-Stationary GEV (NGEV) models, the influence of this parameter is less pronounced, with SDDSI_SUS values of 0.095 and 0.093 for the SSP126 and SSP585 scenarios, respectively. Instead, attention turns to the regression coefficient of the grassland area, associated with the GEV scale parameter. In global sensitivity analysis under the posterior uncertainty scenario (PUS) for parameter inputs, the EDDSI_PUS values for SGEV, NGEV_SSP126, and NGEV_SSP585 models were 0.52, 1.41, and 1.30, respectively, inferring heightened sensitivity of NGEV models to perturbations from entire parameters. It is anticipated that incorporating additional evidence, such as historical flood data, is essential for accurate nonstationary hydrological design to mitigating the influence of parameter uncertainty. The sensitivity indices in this study provide significant insights for assessing the robustness of nonstationary hydrological design in flood risk management and applications.

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Recent advances in simultaneous detection strategies for multi-mycotoxins in foods - Ying Yang; Meng-Yu Ren; Xiao-Guang Xu; Yue Han; Xin Zhao; Chun-Hua Li; Zhi-Lei Zhao (Critical Reviews in Food Science and Nutrition, 2024)

AgNPs-induced oxidative stress and inflammation confer an increased susceptibility to aquatic reovirus infection - Chun Li; Zhiming Liu; Yang Xu; Xiaoying Chen; Qiushi Zhang; Liang Hu; Zhao Lv; Xiaoyan Liu; Tiaoyi Xiao; Deliang Li; Junhua Li (Aquaculture, 2024)

Using network pharmacology and molecular docking to uncover the mechanism by which quercetin alleviates deoxynivalenol-induced porcine intestinal injury - Pu Guo; Xuemin Li; Yunda Xue; Qirong Lu; Yu Liu; Jianglin Xiong; Zhongyuan Wu; Shulin Fu; Chun Ye; Xu Wang; Yinsheng Qiu (Toxicon, 2024)

Association between ambient temperature and mammalian-related injuries in Guangzhou, China, 2014–2019 - Jia-Jun Ma; Ze-Jie Xu; Boheng Liang; Zhou Yang; Li Li; Hao-Neng Huang; Bo-Wen Ming; Pengzhe Qin; Chun-Quan Ou (Science of The Total Environment, 2024)

From disinfection to pathogenicity: Occurrence, resistome risks and assembly mechanism of biocide and metal resistance genes in hospital wastewaters - Chenye Xu; Yibo Zhang; Chun Hu; Chensi Shen; Fang Li; Yumin Xu; Weiping Liu; Dake Shi (Environmental Pollution, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

A multi-functional CoN-Mo2N heterostructure nanorods for high performance lithium-sulfur batteries - Chun Xu; Xiangli Jiang; Minggang Huang; Wei Luo; Shan Zhang; Shuo Zhao; Guochun Li; Jiabiao Lian (Chemical Engineering Journal, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Establishing an efficient micropropagation method for Astragalus membranaceus (Huang Qi) - Thi Ngoc Anh Tran; Feng-Jiao Xu; Jae-Heung Ko; Deok-Chun Yang; Yingping Wang; Li Ling; Dong-Uk Yang; Seok-Kyu Jung (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Potential scale of industrial outputs of the bronze bell casting industry in 500 BCE China - Kin Sum Li; Haiwang Liu; Keith Wilson; Xueqing Chen; Kin San Lee; Qin Fang; Xu Qin; Yu Liu; Tsz Hin Chun; Haoran Jiang (Archaeological and Anthropological Sciences, 2024)
The potential scale of industrial outputs in the ancient world is often underestimated in current archaeological studies due to the lack of surviving artifacts for validation of the production scale. However, production traces left on extant artifacts can help us reconstruct production methods, and thus reveal the potential scale of production outputs of certain industries, even although there may not be a sufficient number of existing artifacts to demonstrate such volumes. The bronze bell casting industry operating in around 500 BCE in Xinzheng in Henan province, China, can be used as an example to demonstrate the then use by bell casters of the “pattern-block method” to efficiently create multiple bells sharing identical components. With their strong focus on efficiency, production speed, and low production costs, these casters intelligently designed assembly lines and assembled identical components replicated from models to prepare molds for casting. Knowledge of their production methods and currently preserved bells can provide evidence that the bell casting industry produced industrial outputs on a massive scale that was rare in the ancient world. This article also shows how innovative methods such as 3D model superimposition can be used to validate these hypotheses.

Multi-scale feature adaptive fusion model for real-time detection in complex citrus orchard environments - Yunfeng Zhang; Li Li; Changpin Chun; Yifeng Wen; Gang Xu (Computers and Electronics in Agriculture, 2024)

Photocatalytic degradation of persistent antibiotic pollutants by MOF-derived bird-nest ferric molybdate - Lian Li; Mengying Xu; Yichao Deng; Jingyan Zheng; Chun He; Pier-Luc Tremblay; Tian Zhang (Journal of Water Process Engineering, 2024)

Study on the mechanism and stability of microbially induced struvite precipitation (MISP) for enhanced immobilization of uranium - Yao-ting Duan; Xin Xu; Lei Niu; Zhe Wang; Xiao-gang Huang; Chun-li Zheng (Journal of Cleaner Production, 2024)

Detecting deck damage in concrete box girder bridges using mode shapes constructed from a moving vehicle - Jian Zhang; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Ya-Fei Wang; Xiu-Dao Mei (Engineering Structures, 2024)

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

o-phenylenediamine Derived Fluorescent Carbon Quantum dots for Detection of Hg(II) in Environmental Water - Anqi Hu; Guoqing Chen; Anlan Huang; Zicheng Cai; Taiqun Yang; Chaoqun Ma; Lei Li; Hui Gao; Jiao Gu; Chun Zhu; Yamin Wu; Xiaoqian Qiu; et al. (Journal of Fluorescence, 2024)

Tryptophan sulfonate: A new chemical marker for accurate and efficient inspection of sulfur-treated food products - Kam-Chun Chan; Wei-Hao Zhang; Yui-Man Chan; Hiu-Lam Li; Jing Fang; Han-Yan Luo; Jun Xu (Food Chemistry, 2024)

Computer vision-based 3D coordinate acquisition of surface feature points of building structures - Chun-Xu Qu; Jin-Zhao Jiang; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2024)

Failure mechanism and deformation forecasting of surrounding rock mass in an underground cavern based on engineering analogy method - Haoyu Mao; Nuwen Xu; Zhong Zhou; Chun Sha; Peiwei Xiao; Biao Li (Tunnelling and Underground Space Technology, 2024)

Trade-offs and synergies among ecosystem services in Inland River Basins under the influence of ecological water transfer project: A case study on the Tarim River basin - Kaixuan Qian; Xiaofei Ma; Wei Yan; Jiaxin Li; Shixian Xu; Yuan Liu; Chun Luo; Wei Yu; Xiaotong Yu; Yahui Wang; Limin Zhou; Yonghui Wang (Science of The Total Environment, 2024)

Lake plastisphere as a new biotope in the Anthropocene: Potential pathogen colonization and distinct microbial functionality - Chenye Xu; Chun Hu; Jiawei Lu; Tong Yang; Chensi Shen; Fang Li; Jie Wang (Journal of Hazardous Materials, 2024)

Prediction model on hydrolysis kinetics of phthalate monoester: A density functional theory study - Tong Xu; Jingwen Chen; Deming Xia; Weihao Tang; Jiansheng Cui; Chun Liu; Shuangjiang Li (Journal of Environmental Sciences, 2024)

The central Qiangtang Metamorphic Belt in northern Tibet is an in-situ Paleo-Tethys Ocean: Evidence from newly discovered Late Devonian radiolarians - Xin Li; Noritoshi Suzuki; Yi-chun Zhang; Hua Zhang; Mao Luo; Dong-xun Yuan; Quan-feng Zheng; Wen-kun Qie; Qi Ju; Feng Qiao; Hai-peng Xu; Xiao-hui Cui (Gondwana Research, 2024)

Study on the performance of Anerinibacillus sp. in degrading cyanide wastewater and its metabolic mechanism - Yao-ting Duan; Wei-da Wang; Si-yuan Qin; Xin Xu; Bo-xi Li; Min-jie Chen; Chun-li Zheng (Chemosphere, 2023)

Paeoniflorin recued hepatotoxicity under zinc oxide nanoparticles exposure via regulation on gut-liver axis and reversal of pyroptosis - Xingyao Pei; Shusheng Tang; Haiyang Jiang; Wenjuan Zhang; Gang Xu; Zonghui Zuo; Zhenhui Ren; Chun Chen; Yao Shen; Cun Li; Daowen Li (Science of The Total Environment, 2023)

Associations between long-term exposure to PM2.5 chemical constituents and allergic diseases: evidence from a large cohort study in China - Chuanteng Feng; Ying Shao; Tingting Ye; Changwei Cai; Chun Yin; Xiaobo Li; Hongyun Liu; Hua Ma; Bin Yu; Mingfang Qin; Yang Chen; Yongfang Yang; et al. (Science of The Total Environment, 2023)

Enhancement of tolerance against flonicamid in Solenopsis invicta (Hymenoptera: Formicidae) through overexpression of CYP6A14 - Tian-yi Zhang; Chang-wei Gong; Jian Pu; An-chun Peng; Xu-yang Li; Yu-meng Wang; Xue-gui Wang (Pesticide Biochemistry and Physiology, 2023)

Optimized design of wind turbine airfoil aerodynamic performance and structural strength based on surrogate model - Qiang Zhang; Weipao Miao; Qingsong Liu; Zifei Xu; Chun Li; Linsen Chang; Minnan Yue (Ocean Engineering, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Origin of the Mussau Trench in the Western Pacific: Geochemical and mineralogical constraints from basalts and serpentinized peridotites - Guoliang Zhang; Junhua Yao; Feng Xu; Tao Wu; Chun-Feng Li; Shuai Wang (Chemical Geology, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Propagation characteristics of acoustic waves in a borehole surrounded by a viscoelastic medium with horizontal cracks - Chong-Wang Yue; Xiao-Chun Li; Ji-Shan Xu; Bo Feng (Applied Geophysics, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Insights into the antibacterial activity and antibacterial mechanism of silver modified fullerene towards Staphylococcus aureus by multiple spectrometric examinations - Yin-Xu Pan; Qiu-Hui Xu; Hua-Ming Xiao; Chun-Ya Li (Chemosphere, 2023)

Electrical stimulation induces anti-tumor immunomodulation via a flexible microneedle-array-integrated interdigital electrode - Yixuan Pan; Yangxi Zhang; Xueying Shi; Dongdong Li; Xiaodan Xu; Bing Xiao; Ying Piao; Jiajia Xiang; Shiqun Shao; Frederic Chun-Yip Ho; Youqing Shen; A. Ping Zhang; et al. (Science Bulletin, 2023)

The improvement of the oxidative oat (Avena sativa L.) protein based on ultrasound treatment: Study of structural, emulsifying, and rheological properties - Yue Xu; Yang Yang; Chun-min Ma; Xin Bian; Li-Kun Ren; Bao-xiang Liu; Lian-zhong Ai; Na Zhang (Food Hydrocolloids, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Sensitive sensing of Hg(II) based on lattice B and surface F co-doped CeO2: Synergies of catalysis and adsorption brought by doping site engineering - Zheng Liu; Xu Xia; Chun-Jie Ye; Huan Xu; Qiu-Yu Wang; Zi-Yi Zheng; Shan-Shan Li; Zhonggang Liu; Zheng Guo (Analytica Chimica Acta, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Ciprofloxacin sorption to purple soil: Potential mechanisms and factors influencing sorption - Guo Chen; Jun Wu; Jing Ma; Min Xu; Lulu Long; Chao Chen; Xiaohong Zhang; Gang Yang; Chun Song; Yinlong Xiao; Peng Gao; Linling Li (Journal of Environmental Chemical Engineering, 2023)

Biocompatible snowman-like tumor-targeting dimer nanoparticles for improved delivery efficiency and enhanced anti-tumor therapy - Chanqi Ye; Xiaoxiao Yan; Xiaomeng Dai; Ruyin Chen; Qiong Li; Shuaishuai Xu; Qi Jiang; Feifei Yan; Suzhen Xu; Chun-Xia Zhao; Peng Zhao; Dong Chen; et al. (Chemical Engineering Journal, 2023)

Association of air pollutants and meteorological factors with tuberculosis: a national multicenter ecological study in China - Qian Wang; Yan-lin Li; Ya-ling Yin; Bin Hu; Chong-chong Yu; Zhen-de Wang; Yu-hong Li; Chun-jie Xu; Yong-bin Wang (International Journal of Biometeorology, 2023)

Label-free and sensitive detection of N6-methyladenosine demethylase activity in crude cell extracts and clinical cancer tissues based on demethylation-triggered exponential signal amplification - Na Li; Lingfei Zhang; Hao Liu; Qinfeng Xu; Fei Ma; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Research progress in steroidal saponins from the genus Polygonatum: Chemical components, biosynthetic pathways and pharmacological effects - Chunfang Xu; Bohou Xia; Zhimin Zhang; Yan Lin; Chun Li; Limei Lin (Phytochemistry, 2023)

Removal of tetracycline in nitrification membrane bioreactors with different ammonia loading rates: Performance, metabolic pathway, and key contributors - Huaihao Xu; Yuepeng Deng; Mingji Li; Kaoming Zhang; Jie Zou; Yunhua Yang; Peng Shi; Yiping Feng; Chun Hu; Zhu Wang (Environmental Pollution, 2023)

An advanced CoNb2O6 anode material with in-situ interstitial doping for high-rate lithium-ion batteries - Shuo Zhao; Ting Chen; Hongping Li; Yuanfeng Liu; Minggang Huang; Chun Xu; Yingxue Cui; Guochun Li; Jiabiao Lian; Yong Wang (Chemical Engineering Journal, 2023)

High-energy and dendrite-free solid-state zinc metal battery enabled by a dual-network and water-confinement hydrogel electrolyte - Zhenglin Li; Guoqiang Zhou; Lei Ye; Jinyu He; Wangwang Xu; Shu Hong; Weimin Chen; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Optical properties and cloud condensation nuclei activity of brown carbon containing α–dicarbonyls and reduced nitrogen compounds - Jiajia Zhou; Chun Xiong; Xiangyu Pei; Binyu Kuang; Zhengning Xu; Fei Zhang; Yao Song; Mei Li; Zhibin Wang (Atmospheric Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Bioreduction of hexavalent chromium via Bacillus subtilis SL-44 enhanced by humic acid: An effective strategy for detoxification and immobilization of chromium - Tao Li; Yanhui He; Jianwen Wang; Huichun Xiang; Xiaolin Xu; Chun Li; Zhansheng Wu (Science of The Total Environment, 2023)

MicroRNA‑30a‑5p regulates cypermethrin-induced apoptosis of Sertoli cells by targeting KLF9 in vitro - Qi Wang; Jia-Fei Xie; Ting-Ting Yao; Xu-Xu Wang; Qian-Wen Guo; Lu-Shan Wang; Yue Yu; Li-Chun Xu (Reproductive Toxicology, 2023)

Dating seafloor spreading of the southwest sub-basin in the South China Sea - Ning Qiu; Zhen Sun; Jian Lin; Chun-Feng Li; Xing Xu (Gondwana Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Mucilage secretion by aerial roots in sorghum (Sorghum bicolor): sugar profile, genetic diversity, GWAS and transcriptomic analysis - Si Xu; Xiu-Qing Li; Hong Guo; Xiao-Yuan Wu; Ning Wang; Zhi-Quan Liu; Huai-Qing Hao; Hai-Chun Jing (Plant Molecular Biology, 2023)

Association between greenspace and cancer: evidence from a systematic review and meta-analysis of multiple large cohort studies - Jiang Li; Yafei Xie; Jianguo Xu; Chun Zhang; Huilin Wang; Danqi Huang; Guoqiang Li; Jinhui Tian (Environmental Science and Pollution Research, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Hierarchical pattern recognition of landform elements considering scale adaptation - Yue-xue Xu; Hong-chun Zhu; Jin-yu Li; Sheng-jia Zhang (Journal of Mountain Science, 2023)

Peak extraction and classification from digital elevation models based on the relationship between morphological characteristics and spatial position - Ming-wei Zhao; Yue Fang; Can-can Yang; Xiao-xiao Ju; Xiao-li Huang; Ling Jiang; Chun Wang; Yan Xu (Journal of Mountain Science, 2023)

Management‐induced changes in soil organic carbon and related crop yield dynamics in China's cropland - Bai‐Jian Lin; Ruo‐Chen Li; Ke‐Chun Liu; Olatunde Pelumi Oladele; Zhi‐Yu Xu; Rattan Lal; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2023)
Enhancing soil organic carbon (SOC) sequestration and food supply are vital for human survival when facing climate change. Site‐specific best management practices (BMPs) are being promoted for adoption globally as solutions. However, how SOC and crop yield are related to each other in responding to BMPs remains unknown. Here, path analysis based on meta‐analysis and machine learning was conducted to identify the effects and potential mechanisms of how the relationship between SOC and crop yield responds to site‐specific BMPs in China. The results showed that BMPs could significantly enhance SOC and maintain or increase crop yield. The maximum benefits in SOC (30.6%) and crop yield (79.8%) occurred in mineral fertilizer combined with organic inputs (MOF). Specifically, the optimal SOC and crop yield would be achieved when the areas were arid, soil pH was ≥7.3, initial SOC content was ≤10 g kg −1 , duration was >10 years, and the nitrogen (N) input level was 100–200 kg ha −1 . Further analysis revealed that the original SOC level and crop yield change showed an inverted V‐shaped structure. The association between the changes in SOC and crop yield might be linked to the positive role of the nutrient‐mediated effect. The results generally suggested that improving the SOC can strongly support better crop performance. Limitations in increasing crop yield still exist due to low original SOC level, and in regions where the excessive N inputs, inappropriate tillage or organic input is inadequate and could be diminished by optimizing BMPs in harmony with site‐specific conditions.

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Facile fabrication of Fe/Zr binary MOFs for arsenic removal in water: High capacity, fast kinetics and good reusability - Qi Guo; Yuan Li; Li-Wei Zheng; Xiao-Yang Wei; Yan Xu; Yi-Wen Shen; Ke-Gang Zhang; Chun-Gang Yuan (Journal of Environmental Sciences, 2023)

The effect of methanol atmosphere and/or H-ZSM-5 catalyst on the thermal upgrading of volatiles generated from Hami lignite pyrolysis - Yun-xin Ma; Yue-lun Wang; Xu Yan; Gui-gui Zhan; Wen-Qi Li; Xue-chun Zhang; Jing-pei Cao (Fuel, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

The effects of serotonergic psychedelics in synaptic and intrinsic properties of neurons in layer II/III of the orbitofrontal cortex - Zi-Hang Tang; Zhi-Peng Yu; Qiong Li; Xiao-Qin Zhang; Kadeliya Muhetaer; Zheng-Chun Wang; Peng Xu; Hao-Wei Shen (Psychopharmacology, 2023)

A Virtual Reality Platform for Context-Dependent Cognitive Research in Rodents - Xue-Tong Qu; Jin-Ni Wu; Yunqing Wen; Long Chen; Shi-Lei Lv; Li Liu; Li-Jie Zhan; Tian-Yi Liu; Hua He; Yu Liu; Chun Xu (Neuroscience Bulletin, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Screening of effective biocontrol agents against postharvest litchi downy blight caused by Peronophythora litchii - Junjian Situ; Li Zheng; Dandan Xu; Chun Gu; Pinggen Xi; Yizhen Deng; Tom Hsiang; Zide Jiang (Postharvest Biology and Technology, 2023)

Novel antioxidant peptide from broken rice resist H2O2-induced premature senescence in 2BS cells via PI3K/Akt and JNK/Bax signaling pathway - Li-kun Ren; Yang Yang; Jing Fan; Chun-min Ma; Xin Bian; Dang-feng Wang; Yue Xu; Bao-xiang Liu; Na Zhang (Food Bioscience, 2023)

Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence - Chun Pan; Yin Wu; Sihan Hu; Ke Li; Xiangyu Liu; Yu Shi; Wenzheng Lin; Xinglong Wang; Yujie Shi; Zhuobin Xu; Huihui Wang; Hao Chen (Environmental Pollution, 2023)

Seismic response study of a steel lattice transmission tower considering the hysteresis characteristics of bolt joint slippage - Jia-Xiang Li; Jin-Peng Cheng; Chao Zhang; Chun-Xu Qu; Xiao-Hong Zhang; Wen-Qiang Jiang (Engineering Structures, 2023)

Natural resources and human development: Role of ICT in testing the resource-curse hypothesis in N11 and BRICS countries - Yi-Wen Li; Wen-Wen Zhang; Bin Zhao; Basil Sharp; Yu Gu; Shi-Chun Xu; Lan-lan Rao (Resources Policy, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

Phenyl-imidazole based and nitrogen rich hyper-crosslinked polymer for sensitive determination of aflatoxins - Mingming Xu; Zhijun Zhou; Lin Hao; Zhi Li; Jie Li; Qianqian Wang; Weihua Liu; Chun Wang; Zhi Wang; Qiuhua Wu (Food Chemistry, 2023)

Polysaccharide of Atractylodes macrocephala Koidz(PAMK) protects against DEHP-induced apoptosis in grass carp hepatocytes - Zongyi Sun; Dejun Li; Haibin Wang; Yu Ding; Chun Zhang; Shuyue Wang; Xuejiao Wang; Bingxin Li; Danning Xu (Fish & Shellfish Immunology, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Application of dual-solvent extraction for separating a low-temperature coal tar: A detailed experimental and quantum chemical study - Zhi-Hao Ma; Sheng Li; Chun Guo; Xue-Qian Dong; Jin-Hu Wang; Min Li; Xian-Hou Guo; Mei-Ling Xu; Xing-Shun Cong; Zhi-Min Zong; Xian-Yong Wei (Fuel, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Effect of β-glucosidase on the aroma of liquid-fermented black tea juice as an ingredient for tea-based beverages - Shuang Liang; Fang Wang; Daniel Granato; Xiaoyu Zhong; An-Feng Xiao; Qun Ye; Lijun Li; Chun Zou; Jun-Feng Yin; Yong-Quan Xu (Food Chemistry, 2023)

A water-gating and zinc-sieving lignocellulose nanofiber separator for dendrite-free rechargeable aqueous zinc ion battery - Zhenglin Li; Lei Ye; Guoqiang Zhou; Wangwang Xu; Kangning Zhao; Xiaoman Zhang; Shu Hong; Tongtong Ma; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

A refined Moho depth model from a joint analysis of gravity and seismic data of the South China Sea basin and its tectonic implications - Liang Huang; Yonglin Wen; Chun-Feng Li; Xi Peng; Zhezhe Lu; Liuna Xu; Yongjian Yao (Physics of the Earth and Planetary Interiors, 2023)

Heavy rare earth element and crustal-derived silicon enrichment in Huayangchuan carbonatites, Qinling orogenic belt - Chun-wan Wei; Cheng Xu; Wen-lei Song; Wei Chen; Aiguo Shi; Zhuoqi Li; Chaoxi Fan (Lithos, 2023)

A pectic polysaccharide from fresh okra (Abelmoschus esculentus L.) beneficially ameliorates CCl4-induced acute liver injury in mice by antioxidation, inhibition of inflammation and modulation of gut microbiota - Jing-Kun Yan; Chun Wang; Ting-Ting Chen; Jie Zhu; Xu Chen; Longqing Li; Xiaozhen Liu; Henan Zhang; Lin Li (Food and Chemical Toxicology, 2023)

Liquid flow behavior in the concentric mesh packing with novel fiber cross-sectional shape in a rotating packed bed - Zhang-Nan Wen; Yan-Bin Li; Han-Zhuo Xu; Ying-Chun Xu; Bao-Chang Sun; Hai-Kui Zou; Guang-Wen Chu (Chemical Engineering Journal, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

Abundant and diverse endophytic bacteria associated with medicinal plant Arctium lappa L. and their potential for host plant growth promoting - Jia-Qi Liu; Shu-Mei Chen; Chun-Mei Zhang; Ming-Jie Xu; Ke Xing; Cheng-Guo Li; Kui Li; Yu-Qin Zhang; Sheng Qin (Antonie van Leeuwenhoek, 2022)

Anatexis of late Neoarchean-Early Paleoproterozoic and late Paleoproterozoic garnet-bearing leucogranite from the Khondalite Belt in the North China Craton - Qiang Shi; Zhong-Yuan Xu; Guo-Chun Zhao; Ding Ding; Guang-Wei Liu; Zhong-Hai Zhao; Jing-Yu Yu; Chen Li; Li-Qiang Bai; Yao Wang; Bing Guo; Kai Zhang; et al. (International Geology Review, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Modal Identification of Structures by Eliminating the Effect of the High Ocean Wind - Chun-Xu Qu; Chang-Chong Liu; Xiao-Mei Yang; Hui-Juan Liu; Hong-Nan Li; Yu-Feng Zhang (Journal of Marine Science and Engineering, 2022)
Tropical cyclone is a rapidly rotating storm system with severe excitation such as high wind. This severe excitation may change the performance of structures, such as bridges, wharves and wind turbine structures. It is very necessary to monitor this important change. Modal parameters are the ones to reflect the structural instinct behavior. However, many identification methods assume that the excitation is white noise, which is not the truth during high ocean wind excitation. Therefore, the modal identification method to deal with severe ocean wind excitation should be investigated. This paper proposes an innovative method to eliminate the effect of high ocean wind on modal identification. The formulation to generate an impulse response is described, where the effect of high wind is pointed. Then the elimination method is derived using the wind velocity spectrum and correlation function. After the wind field is simulated, the wind velocities and spectra at all accelerometer positions are obtained. The real impulse response form is obtained. Then, modal identification using the real impulse response is performed. Finally, a practical cable-stayed bridge is employed and modal identification is performed. The results show that the identified modes can reflect structural real behavior.

Local and remote forcing on the interannual variations of the sedimentary δ15N in Santa Barbara Basin during the past 80 years - Hanyue Xu; Da-Wei Li; Hong-Chun Li; Meixun Zhao; William M. Berelson; Gui’e Jin; Li Li; Satabdi Misra (Frontiers in Marine Science, 2022)
Sedimentary nitrogen isotope (δ 15 N sed ) in Santa Barbara Basin (SBB) has been mostly interpreted as the record of the eastern tropical North Pacific (ETNP) intermediate water denitrification process. Nevertheless, debate remains regarding sources and control mechanisms of δ 15 N sed signal in SBB. Multi-proxy analyses including δ 15 N sed , total organic carbon (TOC), total nitrogen (TN), C/N ratio, and marine biomarkers were performed on a 46-cm sediment core (SBB-190629) collected from SBB in 2019. The core was dated with varve counting and 210 Pb dating method, showing a depositional history of 1938–2019 CE with a sedimentation rate of 0.564 cm/year. The findings show that the δ 15 N sed record (at ~0.25-year resolution) ranges from 6.24‰ to 7.43‰, which was affected by both local and remote forcing. The long-term variations of the SBB δ 15 N sed signature show a general decreasing trend from 1940 to the late 1980s, low values during 1980~2000, and an increase afterward, which is thought to reflect changes in ETNP denitrification induced by the strength of tropical trade winds. Our results also reveal a series of abrupt annual to multiannual changes, superimposed on the long-term variation mentioned above. The SBB local δ 15 N signal (Δδ 15 N SBB ) is accessed by using the deviation from the mean δ 15 N (Δδ 15 N) of SBB-190629 to subtract the Δδ 15 N of the ETNP. The Δδ 15 N SBB record compares well with redox-sensitive proxies (Re/Mo ratio and C 29 stanol/stenol ratio) from the SBB bottom water and with the OC marine content calculated based on the C/N ratio mixing model, indicating that the Δδ 15 N SBB is mainly controlled by bottom water denitrification, which was induced by the change of upwelling intensity and marine productivity. Since various climatic factors (e.g., El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and North Pacific Gyre Oscillation (NPGO)) have different impacts on the upwelling intensity (hence the marine productivity and denitrification) in SBB on different timescales, the influence of combined climatic factors on SBB denitrification is time dependent.

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Alterations to cognitive abilities and functional networks in rats post broad-band intense noise exposure - Xiao-Min Xu; Yu-Qun Zhang; Feng-Chao Zang; Chun-Qiang Lu; Li-Jie Liu; Jian Wang; Richard Salvi; Yu-Chen Chen; Gao-Jun Teng (Brain Imaging and Behavior, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Recent advances in RNA structurome - Bingbing Xu; Yanda Zhu; Changchang Cao; Hao Chen; Qiongli Jin; Guangnan Li; Junfeng Ma; Siwy Ling Yang; Jieyu Zhao; Jianghui Zhu; Yiliang Ding; Xianyang Fang; et al. (Science China Life Sciences, 2022)

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer - Gudongze Li; Haoming Chen; Mingyue Xu; Chun Zhao; Lei Zhong; Rui Li; Yunfei Fu; Yanhong Gao (Advances in Atmospheric Sciences, 2022)
The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations and reanalysis data, the simulation can successfully capture the general features of key meteorological fields over the TP despite slightly underestimating the inflow through the southern TP. The results indicate that the complex topography can decrease the inward and outward moisture transport, ultimately increasing the total net moisture transport into the TP by ∼11%. The impacts of complex topography on precipitation are negligible over the TP, but the spatial distributions of precipitation over the Himalayas are significantly modulated. With the inclusion of complex topography, the sharper southern slopes of the Himalayas shift the lifted airflow and hence precipitation northward compared to the smooth topography. In addition, more small-scale valleys are resolved by the inclusion of complex topography, which serve as channels for moisture transport across the Himalayas, further favoring a northward shift of precipitation. Overall, the difference between the two experiments with different topography datasets is mainly attributed to their differing representation of the degree of the southern slopes of the Himalayas and the extent to which the valleys are resolved.

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Hyperlipidemia patients carrying LDLR splicing mutation c.1187-2A>G respond favorably to rosuvastatin and PCSK9 inhibitor evolocumab - Xiaoyu Zhang; Qianqian Liu; Hongfu Zhang; Chengcheng Tan; Qiangfeng Zhu; Saiyong Chen; Yinglong Du; Haitao Yang; Qingli Li; Chengqi Xu; Chun Wu; Qing K. Wang (Molecular Genetics and Genomics, 2022)

Methods for the construction of DEMs of artificial slopes considering morphological features and semantic information - Yan Xu; Ming-wei Zhao; Jie Lu; Chun Wang; Ling Jiang; Can-can Yang; Xiao-li Huang (Journal of Mountain Science, 2022)

Synthesis, antiproliferative, and antimicrobial properties of novel phthalimide derivatives - Chun-Lan Chi; Lu Xu; Jun-Jie Li; Yang Liu; Bao-Quan Chen (Medicinal Chemistry Research, 2022)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Inhibition of miR-145-5p Reduces Spinal Cord Injury-Induced Inflammatory and Oxidative Stress Responses via Affecting Nurr1-TNF-α Signaling Axis - Lei Jiang; Zeng-Chun Wei; Li-Li Xu; Shan-Ying Yu; Chao Li (Cell Biochemistry and Biophysics, 2021)

Optimization method of first-arrival waveform inversion based on the L-BFGS algorithm - Zhang Kai; Xu Xin; Liu Hong-Xing; Xu Yi-Peng; Li Zhen-Chun; Jiang Ping (Applied Geophysics, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Experimental study on the physico-mechanical properties and temperature field evolution of granite subjected to different heating–cooling treatments - Zhongrui Zhao; Yaoqing Hu; Peihua Jin; Yichen Xu; Yuefei Hu; Chun Li; Qiaorong Meng (Bulletin of Engineering Geology and the Environment, 2021)

Plant-beneficial functions and interactions of Bacillus subtilis SL-44 and Enterobacter cloacae Rs-2 in co-culture by transcriptomics analysis - Yan Li; Yanhui He; Wenfei Wang; Xueping Li; Xiaolin Xu; Xiaochen Liu; Chun Li; Zhansheng Wu (Environmental Science and Pollution Research, 2021)

Do foreign direct investment and environmental regulation improve green technology innovation? An empirical analysis based on panel data from the Chinese manufacturing industry - Shi-Chun Xu; Yun-Fan Li; Jing-Nan Zhang; Yan Wang; Xiao-Xue Ma; Hong-Yu Liu; Hai-Ning Wang; Yuan Tao (Environmental Science and Pollution Research, 2021)

A novel biofilm bioreactor derived from a consortium of acidophilic arsenite-oxidizing bacteria for the cleaning up of arsenite from acid mine drainage - Yifan Xu; Hao Li; Xian-Chun Zeng (Ecotoxicology, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Resting-state causal connectivity of the bed nucleus of the stria terminalis in panic disorder - Manlong Pang; Yuan Zhong; Ziyu Hao; Huazhen Xu; Yun Wu; Changjun Teng; Jian Li; Chaoyong Xiao; Peter T. Fox; Ning Zhang; Chun Wang (Brain Imaging and Behavior, 2021)

FED: a web tool for foreign element detection of genome-edited organism - Qing Liu; Xiaozhen Jiao; Xiangbing Meng; Chun Wang; Cao Xu; Zhixi Tian; Chuanxiao Xie; Genying Li; Jiayang Li; Hong Yu; Kejian Wang (Science China Life Sciences, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Synthesis and antitumor effects of a new class of 1,2,4-triazole derivatives - Zheng Wu; Xin Li; Chun-Lan Chi; Lu Xu; Yong-Yue Sun; Bao-Quan Chen (Medicinal Chemistry Research, 2021)

Response of the Organic Carbon Fractions and Stability of Soil to Alpine Marsh Degradation in Zoige, East Qinghai-Tibet Plateau - Yulin Pu; Chun Ye; Shirong Zhang; Guiyin Wang; Sijia Hu; Xiaoxun Xu; Shuang Xiang; Ting Li; Yongxia Jia (Journal of Soil Science and Plant Nutrition, 2020)

Effects of dietary asafoetida (Ferula sinkiangensis K. M. Shen) levels on feeding attraction activity, growth performance, healthiness, and digestive enzyme activity in juvenile Lateolabrax japonicus - Anle Xu; Jingbo Shang-Guan; Zhongbao Li; Zhan Gao; Yong Chun Huang; Qiang Chen (Fish Physiology and Biochemistry, 2020)

Rho GTPases in cancer radiotherapy and metastasis - Rui-Jie Zeng; Chun-Wen Zheng; Wan-Xian Chen; Li-Yan Xu; En-Min Li (Cancer and Metastasis Reviews, 2020)

Male-biased fasting-induced changes in hepatic tauro-cholic acid and plasma cholesterol in Sult2a8-haplodeficient mice - Kai Wang; Martin Yan-Chun Chan; Jian Xu; Pik-Shan Li; Xing Liu; Angus Yiu-Fai Lee; Susanna Sau-Tuen Lee; Wing-Tai Cheung (Transgenic Research, 2020)

Identification of hybrid green peafowl using mitochondrial and nuclear markers - Han Yu Du; Xin Yuan Zhang; Thi Dao Dinh; Yue Ma; Cheng Zong; Guang Long Li; Thomas D. Dahmer; Yan Chun Xu (Conservation Genetics Resources, 2020)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Petrogenesis of post-collisional magmatism at the Carboniferous–Permian boundary in central Inner Mongolia, NE China: insights into when the Hegenshan Ocean closed? - Lu Lu; Yong Qin; Kai-Jun Zhang; Chun-Yuan Han; Zhuang-Fu Li; Tao Wei; Zheng-Hui Qu; Yong-Zhong Xu (International Geology Review, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Protein extraction and database construction in tea rhizosphere soil - Hai-bin Wang; Chun-lian Zhu; Yu-hua Wang; Qing-xu Zhang; Peng Wang; Ding Li; Xiao-li Jia; Jiang-hua Ye; Hai-bin He (Acta Physiologiae Plantarum, 2020)

What factors influence PM2.5 emissions in China? An analysis of regional differences using a combined method of data envelopment analysis and logarithmic mean Divisia index - Shi-Chun Xu; Yi-Feng Zhou; Chao Feng; Yan Wang; Yun-Fan Li (Environmental Science and Pollution Research, 2020)

Identification and expression profiling analysis of ascorbate peroxidase gene family in Actinidia chinensis (Hongyang) - Guang-Lian Liao; Qing Liu; Yi-Qi Li; Min Zhong; Chun-Hui Huang; Dong-Feng Jia; Xiao-Biao Xu (Journal of Plant Research, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Effects of hourly levels of ambient air pollution on ambulance emergency call-outs in Shenzhen, China - Ting-Ting Chen; Zhi-Ying Zhan; Yi-Min Yu; Li-Jun Xu; Ying Guan; Chun-Quan Ou (Environmental Science and Pollution Research, 2020)

Changes in Starch Synthesis and Metabolism Within Developing Bulbs of Lycoris radiata During the Vegetative Growth Stage - Jun-xu Xu; Qing-zhu Li; Liu-yan Yang; Xin Li; Zhen Wang; Zhen Yang; Yong-chun Zhang (Journal of Plant Growth Regulation, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Antioxidant coumarin and pyrone derivatives from the insect-associated fungus Aspergillus Versicolor - Tian-Xiao Li; Dan-Dan Meng; Ying Wang; Jin-Lu An; Jia-Feng Bai; Xue-Wei Jia; Chun-Ping Xu (Natural Product Research, 2020)

RNA-Seq revealed that infection with white tip nematodes could downregulate rice photosynthetic genes - Hong-Le Wang; Si-Hua Yang; Mei Lv; Shan-Wen Ding; Jun-Yi Li; Chun-Ling Xu; Hui Xie (Functional & Integrative Genomics, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Abundance and residency dynamics of the Indo‐Pacific humpback dolphin, Sousa chinensis , in the Dafengjiang River Estuary, China - Chongwei Peng; Haiping Wu; Xianyan Wang; Qian Zhu; Thomas A. Jefferson; Chun‐Chieh Wang; Youhou Xu; Jian Li; Hu Huang; Mo Chen; Shiang‐Lin Huang (Marine Mammal Science, 2020)
Robust population size estimates are essential for informing population conservation status. Residency dynamics show population habitat use through time. Population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) has been extensively investigated in Chinese waters, but their residency dynamics are rarely known. Mark‐recapture analysis based on photo‐identification records was applied to humpback dolphins in the Dafengjiang River Estuary habitat, one of the key habitats in the northern Beibu Gulf, China. Movement analyses based on lagged identification rate indicated the humpback dolphins spent, on average, 78.5 days inside and 46.9 days outside the survey area. Within the study area, the humpback dolphin abundance was 83 identifiable dolphins. A total of 353–430 humpback dolphins, estimated by POPAN modeling, were involved in this fluid habitat‐use dynamic. Robust Design analysis showed strong seasonality in humpback dolphin abundance and emigration probability, implying a movement‐ and habitat‐use pattern likely associated with spatiotemporal distribution of oceanographic characteristics and prey occurrences. Population surveys and conservation measures currently conducted in Chinese waters seldom consider seasonality in movements between habitat patches, which can be addressed by genetic analyses across habitats and cross‐matching photo‐identification records among neighboring habitats.

ScCas9 recognizes NNG protospacer adjacent motif in genome editing of rice - Yibo Xu; Xiangbing Meng; Junjie Wang; Baoxiang Qin; Kejian Wang; Jiayang Li; Chun Wang; Hong Yu (Science China Life Sciences, 2020)

Design, synthesis, and antitumor evaluation of novel naphthalimide derivatives - Xin Li; Zheng Wu; Lu Xu; Chun-Lan Chi; Bao-Quan Chen (Medicinal Chemistry Research, 2020)

Model test of the influence of cyclic water level fluctuations on a landslide - Chun-can He; Xin-li Hu; Chu Xu; Shuang-shuang Wu; Han Zhang; Chang Liu (Journal of Mountain Science, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Impact of land expropriation on farmers’ livelihoods in the mountainous and hilly regions of Sichuan, China - Shi-li Guo; Chun-jie Li; Ya-li Wei; Kui Zhou; Shao-quan Liu; Ding-de Xu; Qian-yu Li (Journal of Mountain Science, 2019)

Two new polyketides isolated from a diethyl sulphate mutant of marine-derived Penicillium purpurogenum G59 - Chang-Jing Wu; Hua Qiao; Cheng-Bin Cui; Yu Yang; Rui Xu; Chun-Xiao Sun; De-Hai Li; Chang-Wei Li (Natural Product Research, 2019)

Mechanical evolution of constant resistance and large deformation anchor cables and their application in landslide monitoring - Zhigang Tao; Yong Wang; Chun Zhu; Huixia Xu; Gan Li; Manchao He (Bulletin of Engineering Geology and the Environment, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Molecular characterization of heat shock protein 90 from the dinoflagellate Prorocentrum donghaiense and its transcriptional response to thermal, copper and nutrient stresses - Chun Y. Zhang; Guo F. Chen; Yuan Y. Wang; Xu D. Zhang; Cheng H. Li (Marine Biology Research, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Morphology and molecular analysis of Paratylenchus chongqingensis n. sp. (Nematoda: Paratylenchinae) from soil associated with Ophiopogon japonicus in China - Yu Li; Ke Wang; Hui Xie; Chun-Ling Xu (European Journal of Plant Pathology, 2019)

Dynamics of oxytetracycline and resistance genes in soil under long-term intensive compost fertilization in Northern China - Ming Wu; Hui Han; Xiangnan Zheng; Mohan Bai; Ting Xu; Guo-chun Ding; Ji Li (Environmental Science and Pollution Research, 2019)

Integrated rockfall hazard and risk assessment along highways: An example for Jiuzhaigou area after the 2017 Ms 7.0 Jiuzhaigou earthquake, China - Xiao-ning Li; Si-xiang Ling; Chun-wei Sun; Jian-xiang Xu; Tao Huang (Journal of Mountain Science, 2019)

Apple AP2/EREBP transcription factor MdSHINE2 confers drought resistance by regulating wax biosynthesis - Ya-Li Zhang; Chun-Ling Zhang; Gui-Luan Wang; Yong-Xu Wang; Chen-Hui Qi; Chun-Xiang You; Yuan-Yuan Li; Yu-Jin Hao (Planta, 2019)

Genome-wide identification, phylogeny, and expression analysis of Sec14-like PITP gene family in sugarcane - Mao Hua-ying; Wang Wen-ju; Su Wei-hua; Su Ya-chun; Liu Feng; Li Cong-na; Wang Ling; Zhang Xu; Xu Li-ping; Que You-xiong (Plant Cell Reports, 2019)

Yield, nitrogen use efficiency and economic benefits of biochar additions to Chinese Flowering Cabbage in Northwest China - Zhan Wang; Yin-kun Li; Wen-zhong Guo; Zhi-gang Xu; Li-chun Wang; Li Ma (Nutrient Cycling in Agroecosystems, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Molecular surveillance of coxsackievirus A16 reveals the emergence of a new clade in mainland China - Long Chen; Xiang-Jie Yao; Shao-Jian Xu; Hong Yang; Chun-Li Wu; Jing Lu; Wen-Bo Xu; Hai-Long Zhang; Jun Meng; Yong Zhang; Ya-Qing He; Ren-Li Zhang (Archives of Virology, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Global development of the studies focused on antibiotics in aquatic systems from 1945 to 2017 - Chun-Li Zheng; James B Cotner; Chikashi Sato; Gang Li; Yao-Yang Xu (Environmental Science and Pollution Research, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Estimating aboveground biomass using Pléiades satellite image in a karst watershed of Guizhou Province, Southwestern China - Yin-ming Guo; Jian Ni; Li-bin Liu; Yang-yang Wu; Chun-zi Guo; Xin Xu; Qiao-lian Zhong (Journal of Mountain Science, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Short hairpin RNA interference targeting interleukin 1 receptor type I in the paraventricular nucleus attenuates hypertension in rats - Peng Lu; Shu-jun Jiang; Hong Pan; Ai-li Xu; Gui-hua Wang; Chun-lei Ma; Zhen Shi (Pflügers Archiv - European Journal of Physiology, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

RETRACTED ARTICLE: Running bamboo invasion in native and non-native regions worldwide - Qiu-Fang Xu; Chen-Fei Liang; Jun-Hui Chen; Yong-Chun Li; Hua Qin; Jeffry J. Fuhrmann (Biological Invasions, 2017)

Effects of neutral phytase on growth performance and phosphorus utilization in crucian carp (Carassius auratus) - Xin-zheng Nie; Sha Chen; Xiao-xu Zhang; Bin-yang Dai; Li-chun Qian (Journal of Zhejiang University-SCIENCE B, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

Experimental and Numerical Investigation of Permeability Evolution with Damage of Sandstone Under Triaxial Compression - Xu Chen; Jin Yu; Chun’an Tang; Hong Li; Shanyong Wang (Rock Mechanics and Rock Engineering, 2017)

A Brillouin scattering study of hydrous basaltic glasses: the effect of H2O on their elastic behavior and implications for the densities of basaltic melts - Lei Wu; De-Bin Yang; Jun-Xiu Liu; Bo Hu; Hong-Sen Xie; Fang-Fei Li; Yang Yu; Wen-Liang Xu; Chun-Xiao Gao (Physics and Chemistry of Minerals, 2017)

Nuclear magnetic resonance T2 spectrum: multifractal characteristics and pore structure evaluation - Jian-Ping Yan; Xu He; Bin Geng; Qin-Hong Hu; Chun-Zhen Feng; Xiao-Pan Kou; Xing-Wen Li (Applied Geophysics, 2017)

Dating of the topmost terrace in the Jingxian Basin, Anhui Province: an indication of the establishment of the Qingyijiang River - Chun-sheng Hu; Chen-qi Hu; Shao-chen Liu; Guang-lai Xu; Li Wu; Li-hui Yang (Journal of Mountain Science, 2017)

Inhibition of the oxidative stress-induced miR-23a protects the human retinal pigment epithelium (RPE) cells from apoptosis through the upregulation of glutaminase and glutamine uptake - Dan-dan Li; Bin-wu Zhong; Hai-xia Zhang; Hong-yan Zhou; Jie Luo; Yang Liu; Gui-chun Xu; Chun-sheng Luan; Jun Fang (Molecular Biology Reports, 2016)

The inulin-type oligosaccharides extract from morinda officinalis, a traditional Chinese herb, ameliorated behavioral deficits in an animal model of post-traumatic stress disorder - Zhi-Kun Qiu; Chun-Hui Liu; Zhuo-Wei Gao; Jia-Li He; Xu Liu; Qing-Lan Wei; Ji-Sheng Chen (Metabolic Brain Disease, 2016)

Erratum to: NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Impaired SIRT1 promotes the migration of vascular smooth muscle cell-derived foam cells - Ming-Jie Zhang; Yi Zhou; Lei Chen; Xu Wang; Yan Pi; Chun-Yan Long; Meng-Jiao Sun; Xue Chen; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

Characterization of β-glucosidase from Aspergillus terreus and its application in the hydrolysis of soybean isoflavones - Feng-ying Yan; Wei Xia; Xiao-xu Zhang; Sha Chen; Xin-zheng Nie; Li-chun Qian (Journal of Zhejiang University-SCIENCE B, 2016)

Morphology and molecular analysis of Paratylenchus guangzhouensis n. sp. (Nematoda: Paratylenchinae) from the soil associated with Bambusa multiplex in China - Ke Wang; Yu Li; Hui Xie; Chun-Ling Xu; Wen-Jia Wu (European Journal of Plant Pathology, 2016)

Evaluation of the treatment performance and microbial communities of a combined constructed wetland used to treat industrial park wastewater - Ming Xu; Weijing Liu; Chao Li; Chun Xiao; Lili Ding; Ke Xu; Jinju Geng; Hongqiang Ren (Environmental Science and Pollution Research, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Dietary Selenium Status Regulates the Transcriptions of Selenoproteome and Activities of Selenoenzymes in Chicken Kidney at Low or Super-nutritional Levels - Jing-Xiu Xu; Cong Zhang; Chang-Yu Cao; Shi-Yong Zhu; Hui Li; Yan-Chun Sun; Jin-Long Li (Biological Trace Element Research, 2016)

Development time of male and female rotifers with sexual size dimorphism - Xu-Wang Yin; Bing-Bing Tan; Yan-Chun Zhou; Xiao-Chun Li; Wei Liu (Hydrobiologia, 2016)

Morphological and molecular characterisation of Hemicaloosia guangzhouensis n. sp. (Nematoda: Caloosiidae) from China - Ke Wang; Yu Li; Hui Xie; Wen-Jia Wu; Chun-Ling Xu (European Journal of Plant Pathology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Landslide monitoring in southwestern China via time-lapse electrical resistivity tomography - Dong Xu; Xiang-Yun Hu; Chun-Ling Shan; Rui-Heng Li (Applied Geophysics, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Recovery and characterization of homozygous lines from two sweet orange cultivars via anther culture - Shu-Ming Wang; Hong Lan; Hong-Bo Cao; Qiang Xu; Chun-Li Chen; Xiu-Xin Deng; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Identification of two novel critical mutations in PCNT gene resulting in microcephalic osteodysplastic primordial dwarfism type II associated with multiple intracranial aneurysms - Fei-Feng Li; Xu-Dong Wang; Min-Wei Zhu; Zhi-Hong Lou; Qiong Zhang; Chun-Yu Zhu; Hong-Lin Feng; Zhi-Guo Lin; Shu-Lin Liu (Metabolic Brain Disease, 2015)

Indigenous trees restore soil microbial biomass at faster rates than exotic species - Chun Li; Ling-Ling Shi; Anne Ostermann; Jianchu Xu; Yunju Li; Peter E. Mortimer (Plant and Soil, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

SMN is required for the maintenance of embryonic stem cells and neuronal differentiation in mice - Wei-Fang Chang; Jie Xu; Chia-Chun Chang; Shang-Hsun Yang; Hsin-Yang Li; Hsiu Mei Hsieh-Li; Mong-Hsun Tsai; Shinn-Chih Wu; Winston T. K. Cheng; Ji-Long Liu; Li-Ying Sung (Brain Structure and Function, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Chryseobacterium profundimaris sp. nov., a new member of the family Flavobacteriaceae isolated from deep-sea sediment - Lin Xu; Ying-Yi Huo; Zheng-Yang Li; Chun-Sheng Wang; Aharon Oren; Xue-Wei Xu (Antonie van Leeuwenhoek, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Advanced glycation end products induce oxidative stress and mitochondrial dysfunction in SH-SY5Y cells - Xu Wang; Song Yu; Chun-Yan Wang; Yue Wang; Hai-Xing Liu; Yong Cui; Li-De Zhang (In Vitro Cellular & Developmental Biology - Animal, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Pai-1 Gene Variants and COC Use Are Associated with Stroke Risk: A Case-Control Study in the Han Chinese Women - Xiaoping Huang; Ying Li; Zhizheng Huang; Chun Wang; Zhenlin Xu (Journal of Molecular Neuroscience, 2014)

Isolation and characterization of twenty-five polymorphic microsatellite markers in Siniperca scherzeri Steindachner and cross-species amplification - WEI HUANG; XU-FANG LIANG; CHUN-MEI QU; JI LI; LIANG CAO (Journal of Genetics, 2014)

Evaluation of Blattisocius dolichus (Acari: Blattisociidae) for biocontrol of root-knot nematode, Meloidogyne incognita (Tylenchida: Heteroderidae) - Chun-Ling Xu; Yong-Liang Chen; Xue-Nong Xu; Dong-Wei Wang; Hui Xie; En-Dong Wang; Dun-Song Li; Bao-Xin Zhang; Hou-Guo Qin (BioControl, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

GSTP1 Ile105Val polymorphism is associated with lung cancer risk among Asian population and smokers: An updated meta-analysis - Chun-hua Xu; Qin Wang; Ping Zhan; Qian Qian; Li-Ke Yu (Molecular Biology Reports, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Effects on Liver Hydrogen Peroxide Metabolism Induced by Dietary Selenium Deficiency or Excess in Chickens - Jing-Xiu Xu; Chang-Yu Cao; Yan-Chun Sun; Li-Li Wang; Nan Li; Shi-Wen Xu; Jin-Long Li (Biological Trace Element Research, 2014)

The differentiation and development of pistils of hermaphrodites and pistillodes of males in androdioecious Osmanthus fragrans L. and implications for the evolution to androdioecy - Yi-Chun Xu; Li-Hua Zhou; Shao-Qing Hu; Ri-Ming Hao; Chong-jing Huang; Hong-Bo Zhao (Plant Systematics and Evolution, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Fast determination of sulfonamides and their acetylated metabolites from environmental water based on magnetic molecularly imprinted polymers - Haiyan Chen; Yiqun Zhang; Bo Gao; Yang Xu; Qi Zhao; Juan Hou; Jin Yan; Guijie Li; Hui Wang; Lan Ding; Jie Ding; Chun Zhao (Environmental Science and Pollution Research, 2013)

Multiple attenuation using λ-f domain high-resolution Radon transform - Zhi-Na Li; Zhen-Chun Li; Peng Wang; Qiang Xu (Applied Geophysics, 2013)

Stachybotrys from soil in China, identified by morphology and molecular phylogeny - Chun-Yu Jie; Kun Geng; Yu-Lan Jiang; Jun-Jie Xu; Kevin D. Hyde; Eric H. C. McKenzie; Tian-Yu Zhang; Ali H. Bahkali; De-Wei Li; Yong Wang (Mycological Progress, 2013)

Effects of Monogalactoglycerolipid Deficiency and Diacylglycerol Acyltransferase Overexpression on Oil Accumulation in Transgenic Tobacco - Han-Ying Wu; Chao Liu; Min-Chun Li; Ming-Ming Zhao; Dan Gu; Yi-Nong Xu (Plant Molecular Biology Reporter, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Dishevelled-2 silencing reduces androgen-dependent prostate tumor cell proliferation and migration and expression of Wnt-3a and matrix metalloproteinases - Yinhui Yang; Li Jiao; Jianguo Hou; Chuanliang Xu; Linhui Wang; Yongwei Yu; Yun Li; Chun Yang; Xia Wang; Yinghao Sun (Molecular Biology Reports, 2013)

Evaluation of predation abilities of Blattisocius dolichus (Acari: Blattisociidae) on a plant-parasitic nematode, Radopholus similis (Tylenchida: Pratylenchidae) - Yong Liang Chen; Chun Ling Xu; Xue Nong Xu; Hui Xie; Bao Xin Zhang; Hou Guo Qin; Wan Qin Zhou; Dun Song Li (Experimental and Applied Acarology, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Genetic diversity and population structure in wild Sichuan rhesus macaques - Di Yan Li; Huai Liang Xu; Jessica Satkoski Trask; Qing Zhu; An Chun Cheng; David Glenn Smith; Debbie George; Long Zhang (Molecular Biology Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Effect of Fluoride on Insulin Level of Rats and Insulin Receptor Expression in the MC3T3-E1 Cells - Chun-yan Hu; Li-qun Ren; Xi-ning Li; Nan Wu; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2012)

Mapping of quantitative trait loci for oil content in cottonseed kernel - QUAMPAH ALFRED†; HAI YING LIU†; HAI MING XU; JIN RONG LI; JIAN GUO WU; SHUI JIN ZHU; CHUN HAI SHI (Journal of Genetics, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Differential expression of Rs-eng-1b in two populations of Radopholus similis (Tylenchida: Pratylecnchidae) and its relationship to pathogenicity - Chao Zhang; Hui Xie; Chun-Ling Xu; Xi Cheng; Ke-Mei Li; Yu Li (European Journal of Plant Pathology, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Relative bioavailability and pharmacokinetic comparison of two different enteric formulations of omeprazole - Jian Liu; Jian-zhong Shentu; Li-hua Wu; Jing Dou; Qi-yang Xu; Hui-li Zhou; Guo-lan Wu; Ming-zhu Huang; Xing-jiang Hu; Jun-chun Chen (Journal of Zhejiang University-SCIENCE B, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Forest stand biomass estimation using ALOS PALSAR data based on LiDAR-derived prior knowledge in the Qilian Mountain, western China - Qi-Sheng He; Chun-Xiang Cao; Er-Xue Chen; Guo-Qing Sun; Fei-Long Ling; Yong Pang; Hao Zhang; Wen-Jian Ni; Min Xu; Zeng-Yuan Li; Xiao-Wen Li (International Journal of Remote Sensing, 2012)

Survey of antioxidant capacity and phenolic composition of blueberry, blackberry, and strawberry in Nanjing - Wu-yang Huang; Hong-cheng Zhang; Wen-xu Liu; Chun-yang Li (Journal of Zhejiang University-SCIENCE B, 2012)

TP53 codon 72 polymorphism and colorectal cancer susceptibility: a meta-analysis - Jing-Jun Wang; Yuan Zheng; Liang Sun; Li Wang; Peng-Bo Yu; Jian-Hua Dong; Lei Zhang; Jing Xu; Wei Shi; Yu-Chun Ren (Molecular Biology Reports, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Bilobalide Protects Mitochondrial Function in Ovariectomized Rats by Up-regulation of mRNA and Protein Expression of Cytochrome c Oxidase Subunit I - Chun Shi; Juntao Zou; Guoying Li; Zhenying Ge; Zhibin Yao; Jie Xu (Journal of Molecular Neuroscience, 2011)

Fluoride-Induced Oxidative Stress in Three-Dimensional Culture of OS732 Cells and Rats - Hui Liu; Jing-chun Sun; Zhi-tao Zhao; Jin-ming Zhang; Hui Xu; Guang-sheng Li (Biological Trace Element Research, 2011)

Impacts of Spartina alterniflora invasion on abundance and composition of ammonia oxidizers in estuarine sediment - Qiu-Fang Zhang; Jing-Jing Peng; Qian Chen; Xiao-Fang Li; Chun-Yan Xu; Hong-Bing Yin; Shen Yu (Journal of Soils and Sediments, 2011)

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis - Guo-Yun Xu; Pedro S. C. F. Rocha; Man-Ling Wang; Meng-Liang Xu; Yan-Chun Cui; Luo-Ye Li; Yu-Xing Zhu; Xinjie Xia (Planta, 2011)

Proteomic analysis of seed germination under salt stress in soybeans - Xiao-yan Xu; Rui Fan; Rui Zheng; Chun-mei Li; De-yue Yu (Journal of Zhejiang University-SCIENCE B, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Cloning and expression of stearoyl-CoA desaturase 1 (SCD-1) in the liver of the Sichuan white goose and landes goose responding to overfeeding - Zhi-xiong Pan; Chun-chun Han; Ji-wen Wang; Liang Li; Hui Tang; Jia Lv; Lizhi Lu; Feng Xu (Molecular Biology Reports, 2011)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Effects of aluminium on ultrastructure and antioxidant activity in leaves of tea plant - Chunlei Li; Hongmei Xu; Jing Xu; Xiaoya Chun; Dejiang Ni (Acta Physiologiae Plantarum, 2011)

Molecular identification of endophytic fungi from medicinal plant Huperzia serrata based on rDNA ITS analysis - Xu Yu Chen; Yao Dong Qi; Jian He Wei; Zheng Zhang; De Li Wang; Jin Dong Feng; Bing Chun Gan (World Journal of Microbiology and Biotechnology, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Isolation and simultaneous determination of two benzofurans in Radix Eupatorii Chinensis - Xiao-Ling Xie; Xin-Jun Xu; Rui-Ming Li; Jin-Zhi Wan; Chun-Yan Xie; De-Po Yang; Xiao Chen (Natural Product Research, 2010)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Targeted antitumor effect induced by hTERT promoter mediated ODC antisense adenovirus - Wei Wang; Bin Jin; Wei Li; Chun-Xiao Xu; Fu-Ai Cui; Bin Liu; Yun-Fei Yan; Xian-Xi Liu; Xiu-Li Wang (Molecular Biology Reports, 2010)

Developing new SSR markers from ESTs of pea (Pisum sativum L.) - Ya-ming Gong; Sheng-chun Xu; Wei-hua Mao; Qi-zan Hu; Gu-wen Zhang; Ju Ding; Ya-dan Li (Journal of Zhejiang University-SCIENCE B, 2010)

The global image of the Moon obtained by the Chang’E-1: Data processing and lunar cartography - ChunLai Li; JianJun Liu; Xin Ren; LingLi Mou; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; et al. (Science China Earth Sciences, 2010)

CBP knockdown inhibits angiotensin II-induced vascular smooth muscle cells proliferation through downregulating NF-kB transcriptional activity - Jian Yang; Hong Jiang; Si-si Chen; Jing Chen; Sheng-kai Xu; Wan-qiang Li; Ji-chun Wang (Molecular and Cellular Biochemistry, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

Exposure assessment of rainstorm waterlogging on old-style residences in Shanghai based on scenario simulation - Yong Shi; Chun Shi; Shi-Yuan Xu; A-Li Sun; Jun Wang (Natural Hazards, 2010)

EMMPRIN (basigin/CD147) is involved in the morphogenesis of tooth germ in mouse molars - Ming Xie; Ting Jiao; Yuqin Chen; Chun Xu; Jing Li; Xinquan Jiang; Fuqiang Zhang (Histochemistry and Cell Biology, 2010)

Molecular cloning, characterization and expression analysis of PtrHOS1, a novel gene of cold responses from trifoliate orange [Poncirus trifoliata (L.) Raf.] - De-Chun Liu; Li-Gang He; Hui-Liang Wang; Miao Xu; Zhong-Hai Sun (Acta Physiologiae Plantarum, 2010)

Dissipation and Residues of Chlormequat in Wheat and Soil - Xing-li Guo; Chun-hong Jia; Er-cheng Zhao; Yan-jun Xu; Li-jun Han; Shu-ren Jiang (Bulletin of Environmental Contamination and Toxicology, 2010)

Effects of Selenium on the Antioxidant Enzymes Response of Neocaridina heteropoda Exposed to Ambient Nitrite - Hong-wei Wang; Hai-ming Xu; Guo-hua Xiao; Chun-long Zhao; Zi-hui Wang; Duan-bo Cai; Hong-quan Li; Jian-hua Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

Bacterial and archaeal communities in the surface sediment from the northern slope of the South China Sea - Li Liao; Xue-wei Xu; Chun-sheng Wang; Dong-sheng Zhang; Min Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Cloning, expression and reactivating characterization of glycerol dehydratase reactivation factor from Klebsiella pneumoniae XJPD-Li - Gen Lin Zhang; Xiao Lin Xu; Chun Li; BinBin Ma (World Journal of Microbiology and Biotechnology, 2009)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Tissue culture of Sinningia speciosa and analysis of the in vitro-generated tricussate whorled phyllotaxis (twp) variant - Quan-le Xu; Zhe Hu; Chun-yuan Li; Xin-yu Wang; Chong-ying Wang (In Vitro Cellular & Developmental Biology - Plant, 2009)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Synthesis of cyclopropane fatty acid and its effect on freeze-drying survival of Lactobacillus bulgaricus L2 at different growth conditions - Chun Li; Jia-Liang Zhao; Yu-Tang Wang; Xu Han; Ning Liu (World Journal of Microbiology and Biotechnology, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

A Novel Camptothecin Derivative Incorporated in Nano-Carrier Induced Distinguished Improvement in Solubility, Stability and Anti-tumor Activity Both In Vitro and In Vivo - Min Han; Cai-Xia He; Qiu-Li Fang; Xiao-Chun Yang; Yuan-Yuan Diao; Dong-Hang Xu; Qiao-Jun He; Yong-Zhou Hu; Wen-Quan Liang; Bo Yang; Jian-Qing Gao (Pharmaceutical Research, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Study of Antibacterial Activity of ZnZnbisporphyrin Complexes and its Free Components on Staphylococcus aureus by Microcalorimetry - Xiang-jiao Xu; Chun-qiao Chen; Zhuo-yuan Wang; Yi Zhang; An-xin Hou; Chao-Hong Li; Yi Liu (Biological Trace Element Research, 2009)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Twelve polymorphic microsatellite loci for Achnatherum inebrians (Poaceae) - Na Chen; Yan-Zhuo Yang; Xiao-li Yang; Xing-xu Zhang; Chun-jie Li (Conservation Genetics, 2008)

Pregnane glycosides and steroid saponins from Smilax bockii Warb. and their NGF-potentiating activity - Jing Xu; Xian Li; Chun Chao Zhao; Yi Wang (Natural Product Research, 2008)

Improvement of xylanase production by Aspergillus niger XY-1 using response surface methodology for optimizing the medium composition - Yao-xing Xu; Yan-li Li; Shao-chun Xu; Yong Liu; Xin Wang; Jiang-wu Tang (Journal of Zhejiang University-SCIENCE B, 2008)

Role of Oxidative Stress in Osteoblasts Exposed to Sodium Fluoride - Hui Xu; Chun-hong Wang; Zhi-tao Zhao; Wen-bo Zhang; Guang-sheng Li (Biological Trace Element Research, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Synthesis and structure characterization of new 1,2,4-oxadiazolo[4,5-d]-1,5-benzothiazepines derivatives containing 2-phenyl-1,2,3-triazole through 1,3-dipolar cycloaddition reaction - De-Bao Yang; Fang-Ming Liu; Feng Xu; Chun Yang; Jia-Wei Ye; Song-Wei Shen; Ying-Lei Zhou; Wei Li (Molecular Diversity, 2008)

Contrasting chemical and isotopic compositions of organic matter in Changjiang (Yangtze River) estuarine and East China Sea shelf sediments - Xu-Chen Wang; Ming-Yi Sun; An-Chun Li (Journal of Oceanography, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Recombination and genetic differentiation among natural populations of the ectomycorrhizal mushroom Tricholoma matsutake from southwestern China - JIANPING XU; TAO SHA; YAN‐CHUN LI; ZHI‐WEI ZHAO; ZHU L. YANG (Molecular Ecology, 2008)
Effective conservation and utilization strategies for natural biological resources require a clear understanding of the natural populations of the target organisms. Tricholoma matsutake is an ectomycorrhizal mushroom that forms symbiotic associations with plants and plays an important ecological role in natural forest ecosystems in many parts of the world. It is also an economically very important gourmet mushroom. Because no artificial cultivation is available, natural populations of this species are under increasing threats, primarily from habitat disturbance and destruction. Despite its economical and ecological importance, little is known about its genetics and population biology. Here, using 14 polymerase chain reaction–restriction fragment length polymorphism markers, we analysed 154 strains from 17 geographical locations in southwestern China, a region where over 25% of the global T. matsutake harvest comes from. Our results revealed abundant genetic variation within individual populations. The analyses of gene and genotype frequencies within populations indicated that most loci did not deviate from Hardy–Weinberg equilibrium in most populations and that alleles among loci were in linkage equilibrium in the majority of the local populations. These results are consistent with the hypothesis that sexual reproduction and recombination play an important role in natural populations of this species. Our analyses indicated low but significant genetic differentiation among the geographical populations, with a significant positive correlation between genetic distance and geographical distance. We discuss the implications of our results to the ecology and resource management of this species.

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Improvement of echinacoside and acteoside production by two-stage elicitation in cell suspension culture of Cistanche deserticola - Wen-Hao Chen; Chun-Ming Xu; Jian-Li Zeng; Bing Zhao; Xiao-Dong Wang; Yu-Chun Wang (World Journal of Microbiology and Biotechnology, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

QTL mapping for economic traits based on a dense genetic map of cotton with PCR-based markers using the interspecific cross of Gossypium hirsutum × Gossypium barbadense - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Yan-Xin Zhang; Wu Li (Euphytica, 2007)

A new anthraquinone from Galium verum L. - Chun-Chao Zhao; Jian-Hua Shao; Xian Li; Jing Xu; Jin-Hui Wang (Natural Product Research, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Isolation and Characterization of a Carbendazim-Degrading Rhodococcus sp. djl-6 - Xu Jing-Liang; Gu Xiang-Yang; Shen Biao; Wang Zhi-Chun; Wang Kun; Li Shun-Peng (Current Microbiology, 2006)

Gis supported hedonic model for assessing property value in west Oakland, California - De-min Zhou; Jian-chun Xu; Hui-li Gong (Chinese Geographical Science, 2006)

The impact of NiO on microstructure and electrical property of solid oxide fuel cell anode - Yan Li; Zhong-yang Luo; Chun-jiang Yu; Dan Luo; Zhu-an Xu; Ke-fa Cen (Journal of Zhejiang University-SCIENCE B, 2005)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Intestinal microflora in rats with ischemia/reperfusion liver injury - Hui-chun Xing; Lan-juan Li; Kai-jin Xu; Tian Shen; Yun-bo Chen; Ji-fang Sheng; Yun-song Yu; Ya-gang Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Studies on the relation between the fast phase of millisecond delayed light emission and the proton released from oxidation of water in spinach chloroplast - Jia-Mian Wei; Jin Shi; Chun-He Xu; De-Yao Li; Yun-Kang Shen (Photosynthesis Research, 1998)